Study of Fe (Se, Te) micron-sized rings by magnetic force microscopy - Polshyn, Hryhoriy; Zhang, Can; Naibert, Tyler; Eckstein, James; Budakian, Raffi (APS March Meeting 2015)
The study of fluxoid states and fluxoid dynamics in mesoscopic iron-based superconducting rings is valuable for characterizing the basic properties of the superconductor, and may also provide important insight into the superconducting paring symmetry. We report the fabrications of micron-sized rings and disks from thin films of Fe(Se, Te) grown by molecular beam epitaxy. In order to study fluxoid states in rings we developed a custom-tailored version of magnetic force microscopy (MFM). This technique has a number of qualitative advantages for working with mesoscopic superconducting samples in comparison to the conventional MFM and other imaging techniques. We observed metastable fluxoid states in rings of different sizes. Thermally activated fluxoid dynamics of these states was studied and modeled. In addition, we found different regimes of interaction between Fe(Se, Te) ring and MFM tip which are explained. Possibilities of the existence of exotic vortex states and proposals for experiments to test the symmetry of the superconducting order parameter in iron based superconductors are analyzed.

Bayesian inference for stochastic individual-based models of ecological systems: a pest control simulation study - Parise, Francesca; Lygeros, John; Ruess, Jakob (Frontiers in Environmental Science)
Mathematical models are of fundamental importance in the understanding of complex population dynamics. For instance, they can be used to predict the population evolution starting from different initial conditions or to test how a system responds to external perturbations. For this analysis to be meaningful in real applications, however, it is of paramount importance to choose an appropriate model structure and to infer the model parameters from measured data. While many parameter inference methods are available for models based on deterministic ordinary differential equations, the same does not hold for more detailed individual-based models. Here we consider, in particular, stochastic models in which the time evolution of the species abundances is described by a continuous-time Markov chain. These models are governed by a master equation that is typically difficult to solve. Consequently, traditional inference methods that rely on iterative evaluation of parameter likelihoods are computationally intractable. The aim of this paper is to present recent advances in parameter inference for continuous-time Markov chain models, based on a moment closure approximation of the parameter likelihood, and to investigate how these results can help in understanding, and ultimately controlling, complex systems in ecology. Specifically, we illustrate through an agricultural pest case study how parameters of a stochastic individual-based model can be identified from measured data and how the resulting model can be used to solve an optimal control problem in a stochastic setting. In particular, we show how the matter of determining the optimal combination of two different pest control methods can be formulated as a chance constrained optimization problem where the control action is modeled as a state reset, leading to a hybrid system formulation.
Keywords: General Environmental Science

Directly reprogrammed human neurons retain aging-associated transcriptomic signatures and reveal age-related nucleocytoplasmic defects - Mertens, Jerome; Paquola, Apuã C.M.; Ku, Manching; Hatch, Emily; Böhnke, Lena; Ladjevardi, Shauheen; McGrath, Sean; Campbell, Benjamin; Lee, Hyungjun; Herdy, Joseph R.; Gonçalves, J. Tiago; Toda, Tomohisa; et al. (Cell Stem Cell)
Aging is a major risk factor for many human diseases, and in vitro generation of human neurons is an attractive approach for modeling aging-related brain disorders. However, modeling aging in differentiated human neurons has proved challenging. We generated neurons from human donors across a broad range of ages, either by iPSC-based reprogramming and differentiation or by direct conversion into induced neurons (iNs). While iPSCs and derived neurons did not retain aging-associated gene signatures, iNs displayed age-specific transcriptional profiles and revealed age-associated decreases in the nuclear transport receptor RanBP17. We detected an age-dependent loss of nucleocytoplasmic compartmentalization (NCC) in donor fibroblasts and corresponding iNs and found that reduced RanBP17 impaired NCC in young cells, while iPSC rejuvenation restored NCC in aged cells. These results show that iNs retain important aging-related signatures, thus allowing modeling of the aging process in vitro, and they identify impaired NCC as an important factor in human aging.
Keywords: Cell Biology; Genetics; Molecular Medicine

The nucleoporin Nup153 regulates embryonic stem cell pluripotency through gene silencing - Jacinto, Filipe V.; Benner, Chris; HETZER, Martin W (Genes & Development)
Nucleoporins (Nups) are a family of proteins best known as the constituent building blocks of nuclear pore complexes (NPCs), membrane-embedded channels that mediate nuclear transport across the nuclear envelope. Recent evidence suggests that several Nups have additional roles in controlling the activation and silencing of developmental genes; however, the mechanistic details of these functions remain poorly understood. Here, we show that depletion of Nup153 in mouse embryonic stem cells (mESCs) causes the derepression of developmental genes and induction of early differentiation. This loss of stem cell identity is not associated with defects in the nuclear import of key pluripotency factors. Rather, Nup153 binds around the transcriptional start site (TSS) of developmental genes and mediates the recruitment of the polycomb-repressive complex 1 (PRC1) to a subset of its target loci. Our results demonstrate a chromatin-associated role of Nup153 in maintaining stem cell pluripotency by functioning in mammalian epigenetic gene silencing.
Keywords: Developmental Biology; Genetics

Integrated transcriptome and proteome analyses reveal organ-specific proteome deterioration in old rats - Ori, Alessandro; Toyama, Brandon H.; Harris, Michael S.; Bock, Thomas; Iskar, Murat; Bork, Peer; Ingolia, Nicholas T.; HETZER, Martin W; Beck, Martin (Cell Systems)
Aging is associated with the decline of protein, cell, and organ function. Here, we use an integrated approach to characterize gene expression, bulk translation, and cell biology in the brains and livers of young and old rats. We identify 468 differences in protein abundance between young and old animals. The majority are a consequence of altered translation output, that is, the combined effect of changes in transcript abundance and translation efficiency. In addition, we identify 130 proteins whose overall abundance remains unchanged but whose sub-cellular localization, phosphorylation state, or splice-form varies. While some protein-level differences appear to be a generic property of the rats’ chronological age, the majority are specific to one organ. These may be a consequence of the organ’s physiology or the chronological age of the cells within the tissue. Taken together, our study provides an initial view of the proteome at the molecular, sub-cellular, and organ level in young and old rats.
Keywords: Cell Biology; Histology; Pathology and Forensic Medicine

Nuclear pore proteins and the control of genome functions - Ibarra, Arkaitz; HETZER, Martin W (Genes & Development)
Nuclear pore complexes (NPCs) are composed of several copies of ∼30 different proteins called nucleoporins (Nups). NPCs penetrate the nuclear envelope (NE) and regulate the nucleocytoplasmic trafficking of macromolecules. Beyond this vital role, NPC components influence genome functions in a transport-independent manner. Nups play an evolutionarily conserved role in gene expression regulation that, in metazoans, extends into the nuclear interior. Additionally, in proliferative cells, Nups play a crucial role in genome integrity maintenance and mitotic progression. Here we discuss genome-related functions of Nups and their impact on essential DNA metabolism processes such as transcription, chromosome duplication, and segregation.
Keywords: Developmental Biology; Genetics

Linking micronuclei to chromosome fragmentation - Hatch, Emily M.; HETZER, Martin W (Cell)
Human cancer cells bear complex chromosome rearrangements that can be potential drivers of cancer development. However, the molecular mechanisms underlying these rearrangements have been unclear. Zhang et al. use a new technique combining live-cell imaging and single-cell sequencing to demonstrate that chromosomes mis-segregated to micronuclei frequently undergo chromothripsis-like rearrangements in the subsequent cell cycle.
Keywords: General Biochemistry; Genetics and Molecular Biology

Chromothripsis - Hatch, Emily M.; HETZER, Martin W (Current Biology)
Keywords: General Agricultural and Biological Sciences; General Biochemistry; Genetics and Molecular Biology

Evidence for PopIII-like stellar populations in the most luminous Lyα emitters at the epoch of reionisation: Spectroscopic confirmation - Sobral, David; Matthee, Jorryt J; Darvish, Behnam; Schaerer, Daniel; Mobasher, Bahram; Röttgering, Huub; Santos, Sérgio; Hemmati, Shoubaneh (The Astrophysical Journal)
Faint Lyα emitters become increasingly rarer toward the reionization epoch (z ∼ 6–7). However, observations from a very large (∼5 deg2) Lyα narrow-band survey at z = 6.6 show that this is not the case for the most luminous emitters, capable of ionizing their own local bubbles. Here we present follow-up observations of the two most luminous Lyα candidates in the COSMOS field: “MASOSA” and “CR7.” We used X-SHOOTER, SINFONI, and FORS2 on the Very Large Telescope, and DEIMOS on Keck, to confirm both candidates beyond any doubt. We find redshifts of z = 6.541 and z = 6.604 for “MASOSA” and “CR7,” respectively. MASOSA has a strong detection in Lyα with a line width of 386 ± 30 km s−1 (FWHM) and with very high EW0 (>200 Å), but undetected in the continuum, implying very low stellar mass and a likely young, metal-poor stellar population. “CR7,” with an observed Lyα luminosity of 1043.92±0.05 erg s−1 is the most luminous Lyα emitter ever found at z > 6 and is spatially extended (∼16 kpc). “CR7” reveals a narrow Lyα line with 266 ± 15 km s−1 FWHM, being detected in the near-infrared (NIR) (rest-frame UV; β = −2.3 ± 0.1) and in IRAC/Spitzer. We detect a narrow He II 1640 Å emission line (6σ, FWHM = 130 ± 30 km s−1 ) in CR7 which can explain the clear excess seen in the J-band photometry (EW0 ∼ 80 Å). We find no other emission lines from the UV to the NIR in our X-SHOOTER spectra (He II/O III] 1663 Å > 3 and He II/C III] 1908 Å > 2.5). We conclude that CR7 is best explained by a combination of a PopIII-like population, which dominates the rest-frame UV and the nebular emission, and a more normal stellar population, which presumably dominates the mass. Hubble Space Telescope/WFC3 observations show that the light is indeed spatially separated between a very blue component, coincident with Lyα and He II emission, and two red components (∼5 kpc away), which dominate the mass. Our findings are consistent with theoretical predictions of a PopIII wave, with PopIII star formation migrating away from the original sites of star formation.
Keywords: Space and Planetary Science; Astronomy and Astrophysics; dark ages; reionization; first stars – early universe – galaxies: evolution

CF-HiZELS, an ∼10 deg2 emission-line survey with spectroscopic follow-up: Hα, [O III] + Hβ and [O II] luminosity functions at z = 0.8, 1.4 and 2.2 - Sobral, D.; Matthee, Jorryt J; Best, P. N.; Smail, I.; Khostovan, A. A.; Milvang-Jensen, B.; Kim, J.-W.; Stott, J.; Calhau, J.; Nayyeri, H.; Mobasher, B. (Monthly Notices of the Royal Astronomical Society)
We present results from the largest contiguous narrow-band survey in the near-infrared. We have used the wide-field infrared camera/Canada–France–Hawaii Telescope and the lowOH2 filter (1.187 ± 0.005 μm) to survey ≈10 deg2 of contiguous extragalactic sky in the SA22 field. A total of ∼6000 candidate emission-line galaxies are found. We use deep ugrizJK data to obtain robust photometric redshifts. We combine our data with the High-redshift(Z) Emission Line Survey (HiZELS), explore spectroscopic surveys (VVDS, VIPERS) and obtain our own spectroscopic follow-up with KMOS, FMOS and MOSFIRE to derive large samples of high-redshift emission-line selected galaxies: 3471 Hα emitters at z = 0.8, 1343 [O III] + Hβ emitters at z = 1.4 and 572 [O II] emitters at z = 2.2. We probe comoving volumes of >106 Mpc3 and find significant overdensities, including an 8.5σ (spectroscopically confirmed) overdensity of Hα emitters at z = 0.81. We derive Hα, [O III] + Hβ and [O II] luminosity functions at z = 0.8, 1.4, 2.2, respectively, and present implications for future surveys such as Euclid. Our uniquely large volumes/areas allow us to subdivide the samples in thousands of randomized combinations of areas and provide a robust empirical measurement of sample/cosmic variance. We show that surveys for star-forming/emission-line galaxies at a depth similar to ours can only overcome cosmic-variance (errors <10 per cent) if they are based on volumes >5 × 105 Mpc3; errors on L* and ϕ* due to sample (cosmic) variance on surveys probing ∼104 and ∼105 Mpc3 are typically very high: ∼300 and ∼40–60 per cent, respectively.
Keywords: Space and Planetary Science; Astronomy and Astrophysics; galaxies: evolution; galaxies: formation; galaxies: luminosity function; mass function; cosmology: observations; early Universe; large-scale structure of Universe

Identification of the brightest Lyα emitters at z = 6.6: implications for the evolution of the luminosity function in the reionization era - Matthee, Jorryt J; Sobral, David; Santos, Sérgio; Röttgering, Huub; Darvish, Behnam; Mobasher, Bahram (Monthly Notices of the Royal Astronomical Society)
Using wide-field narrow-band surveys, we provide a new measurement of the z = 6.6 Lymanα emitter (LAE) luminosity function (LF), which constraints the bright end for the first time. We use a combination of archival narrow-band NB921 data in UDS and new NB921 measurements in SA22 and COSMOS/UltraVISTA, all observed with the Subaru telescope, with a total area of ∼5 deg2. We exclude lower redshift interlopers by using broad-band optical and near-infrared photometry and also exclude three supernovae with data split over multiple epochs. Combining the UDS and COSMOS samples, we find no evolution of the bright end of the Lyα LF between z = 5.7 and 6.6, which is supported by spectroscopic follow-up, and conclude that sources with Himiko-like luminosity are not as rare as previously thought, with number densities of ∼1.5 × 10−5 Mpc−3. Combined with our wide-field SA22 measurements, our results indicate a non-Schechter-like bright end of the LF at z = 6.6 and a different evolution of observed faint and bright LAEs, overcoming cosmic variance. This differential evolution is also seen in the spectroscopic follow-up of UV-selected galaxies and is now also confirmed for LAEs, and we argue that it may be an effect of reionization. Using a toy model, we show that such differential evolution of the LF is expected, since brighter sources are able to ionize their surroundings earlier, such that Lyα photons are able to escape. Our targets are excellent candidates for detailed follow-up studies and provide the possibility to give a unique view on the earliest stages in the formation of galaxies and reionization process.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

The brightest Lyα emitter: Pop III or black hole? - Pallottini, A.; Ferrara, A.; Pacucci, F.; Gallerani, S.; Salvadori, S.; Schneider, R.; Schaerer, D.; Sobral, D.; Matthee, Jorryt J (Monthly Notices of the Royal Astronomical Society)
CR7 is the brightest z = 6.6 Ly α emitter (LAE) known to date, and spectroscopic follow-up by Sobral et al. suggests that CR7 might host Population (Pop) III stars. We examine this interpretation using cosmological hydrodynamical simulations. Several simulated galaxies show the same ‘Pop III wave’ pattern observed in CR7. However, to reproduce the extreme CR7 Ly α/He II1640 line luminosities (⁠Lα/HeII⁠) a top-heavy initial mass function and a massive ( ≳ 107 M⊙) Pop III burst with age ≲ 2 Myr are required. Assuming that the observed properties of Ly α and He II emission are typical for Pop III, we predict that in the COSMOS/UDS/SA22 fields, 14 out of the 30 LAEs at z = 6.6 with Lα > 1043.3 erg s−1 should also host Pop III stars producing an observable LHeII≳1042.7ergs−1⁠. As an alternate explanation, we explore the possibility that CR7 is instead powered by accretion on to a direct collapse black hole. Our model predicts Lα, LHeII⁠, and X-ray luminosities that are in agreement with the observations. In any case, the observed properties of CR7 indicate that this galaxy is most likely powered by sources formed from pristine gas. We propose that further X-ray observations can distinguish between the two above scenarios.
Keywords: Space and Planetary Science; Astronomy and Astrophysics; black hole physics; stars: Population III; galaxies: high-redshift

On multiple keyword sponsored search auctions with budgets - Colini-Baldeschi, Riccardo; Leonardi, Stefano; Henzinger, Monika H; Starnberger, Martin (ACM Transactions on Economics and Computation)
We study multiple keyword sponsored search auctions with budgets. Each keyword has multiple ad slots with a click-through rate. The bidders have additive valuations, which are linear in the click-through rates, and budgets, which are restricting their overall payments. Additionally, the number of slots per keyword assigned to a bidder is bounded. We show the following results: (1) We give the first mechanism for multiple keywords, where click-through rates differ among slots. Our mechanism is incentive compatible in expectation, individually rational in expectation, and Pareto optimal. (2) We study the combinatorial setting, where each bidder is only interested in a subset of the keywords. We give an incentive compatible, individually rational, Pareto-optimal, and deterministic mechanism for identical click-through rates. (3) We give an impossibility result for incentive compatible, individually rational, Pareto-optimal, and deterministic mechanisms for bidders with diminishing marginal valuations.
Keywords: Algorithms; Economics; Clinching ascending auction; auctions with budgets; Sponsored search auctions

Auctions for heterogeneous items and budget limits - Dütting, Paul; Henzinger, Monika H; Starnberger, Martin (ACM Transactions on Economics and Computation)
We study individual rational, Pareto-optimal, and incentive compatible mechanisms for auctions with heterogeneous items and budget limits. We consider settings with multiunit demand and additive valuations. For single-dimensional valuations we prove a positive result for randomized mechanisms, and a negative result for deterministic mechanisms. While the positive result allows for private budgets, the negative result is for public budgets. For multidimensional valuations and public budgets we prove an impossibility result that applies to deterministic and randomized mechanisms. Taken together this shows the power of randomization in certain settings with heterogeneous items, but it also shows its limitations.
Keywords: Algorithmic game theory; auction theory; Clinching auction; Pareto optimality; Budget limits

Combinatorial auctions with conflict-based externalities - Cheung, Yun Kuen; Henzinger, Monika H; Hoefer, Martin; Starnberger, Martin (11th International Conference on Web and Internet Economics)
Combinatorial auctions (CA) are a well-studied area in algorithmic mechanism design. However, contrary to the standard model, empirical studies suggest that a bidder’s valuation often does not depend solely on the goods assigned to him. For instance, in adwords auctions an advertiser might not want his ads to be displayed next to his competitors’ ads. In this paper, we propose and analyze several natural graph-theoretic models that incorporate such negative externalities, in which bidders form a directed conflict graph with maximum out-degree Δ. We design algorithms and truthful mechanisms for social welfare maximization that attain approximation ratios depending on Δ. For CA, our results are twofold: (1) A lottery that eliminates conflicts by discarding bidders/items independent of the bids. It allows to apply any truthful 𝛼-approximation mechanism for conflict-free valuations and yields an 𝒪(𝛼Δ)-approximation mechanism. (2) For fractionally sub-additive valuations, we design a rounding algorithm via a novel combination of a semi-definite program and a linear program, resulting in a cone program; the approximation ratio is 𝒪((ΔloglogΔ)/logΔ). The ratios are almost optimal given existing hardness results. For adwords auctions, we present several algorithms for the most relevant scenario when the number of items is small. In particular, we design a truthful mechanism with approximation ratio 𝑜(Δ) when the number of items is only logarithmic in the number of bidders.

Ad exchange: Envy-free auctions with mediators - Ben-Zwi, Oren; Henzinger, Monika H; Loitzenbauer, Veronika (11th International Conference on Web and Internet Economics)
Ad exchanges are an emerging platform for trading advertisement slots on the web with billions of dollars revenue per year. Every time a user visits a web page, the publisher of that web page can ask an ad exchange to auction off the ad slots on this page to determine which advertisements are shown at which price. Due to the high volume of traffic, ad networks typically act as mediators for individual advertisers at ad exchanges. If multiple advertisers in an ad network are interested in the ad slots of the same auction, the ad network might use a “local” auction to resell the obtained ad slots among its advertisers. In this work we want to deepen the theoretical understanding of these new markets by analyzing them from the viewpoint of combinatorial auctions. Prior work studied mostly single-item auctions, while we allow the advertisers to express richer preferences over multiple items. We develop a game-theoretic model for the entanglement of the central auction at the ad exchange with the local auctions at the ad networks. We consider the incentives of all three involved parties and suggest a three-party competitive equilibrium, an extension of the Walrasian equilibrium that ensures envy-freeness for all participants. We show the existence of a three-party competitive equilibrium and a polynomial-time algorithm to find one for gross-substitute bidder valuations.

Improved algorithms for decremental single-source reachability on directed graphs - Henzinger, Monika H; Krinninger, Sebastian; Nanongkai, Danupon (42nd International Colloquium on Automata, Languages and Programming)
Recently we presented the first algorithm for maintaining the set of nodes reachable from a source node in a directed graph that is modified by edge deletions with 𝑜(𝑚𝑛) total update time, where 𝑚 is the number of edges and 𝑛 is the number of nodes in the graph [Henzinger et al. STOC 2014]. The algorithm is a combination of several different algorithms, each for a different 𝑚 vs. 𝑛 trade-off. For the case of 𝑚=Θ(𝑛1.5) the running time is 𝑂(𝑛2.47), just barely below 𝑚𝑛=Θ(𝑛2.5). In this paper we simplify the previous algorithm using new algorithmic ideas and achieve an improved running time of 𝑂̃ (min(𝑚7/6𝑛2/3,𝑚3/4𝑛5/4+𝑜(1),𝑚2/3𝑛4/3+𝑜(1)+𝑚3/7𝑛12/7+𝑜(1))). This gives, e.g., 𝑂(𝑛2.36) for the notorious case 𝑚=Θ(𝑛1.5). We obtain the same upper bounds for the problem of maintaining the strongly connected components of a directed graph undergoing edge deletions. Our algorithms are correct with high probabililty against an oblivious adversary.

Finding 2-edge and 2-vertex strongly connected components in quadratic time - Henzinger, Monika H; Krinninger, Sebastian; Loitzenbauer, Veronika (2nd International Colloquium on Automata, Languages and Programming)
We present faster algorithms for computing the 2-edge and 2-vertex strongly connected components of a directed graph. While in undirected graphs the 2-edge and 2-vertex connected components can be found in linear time, in directed graphs with m edges and n vertices only rather simple O(m n)-time algorithms were known. We use a hierarchical sparsification technique to obtain algorithms that run in time 𝑂(𝑛2). For 2-edge strongly connected components our algorithm gives the first running time improvement in 20 years. Additionally we present an 𝑂(𝑚2/log𝑛)-time algorithm for 2-edge strongly connected components, and thus improve over the O(m n) running time also when 𝑚=𝑂(𝑛). Our approach extends to k-edge and k-vertex strongly connected components for any constant k with a running time of 𝑂(𝑛2log𝑛) for k-edge-connectivity and 𝑂(𝑛3) for k-vertex-connectivity.

Online ad assignment with an ad exchange - Dvořák, Wolfgang; Henzinger, Monika H (12th International Workshop of Approximation and Online Algorithms)
Ad exchanges are becoming an increasingly popular way to sell advertisement slots on the internet. An ad exchange is basically a spot market for ad impressions. A publisher who has already signed contracts reserving advertisement impressions on his pages can choose between assigning a new ad impression for a new page view to a contracted advertiser or to sell it at an ad exchange. This leads to an online revenue maximization problem for the publisher. Given a new impression to sell decide whether (a) to assign it to a contracted advertiser and if so to which one or (b) to sell it at the ad exchange and if so at which reserve price. We make no assumptions about the distribution of the advertiser valuations that participate in the ad exchange and show that there exists a simple primal-dual based online algorithm, whose lower bound for the revenue converges to 𝑅𝐴𝐷𝑋+𝑅𝐴(1−1/𝑒), where 𝑅𝐴𝐷𝑋 is the revenue that the optimum algorithm achieves from the ad exchange and 𝑅𝐴 is the revenue that the optimum algorithm achieves from the contracted advertisers.

Design of dynamic algorithms via primal-dual method - Bhattacharya, Sayan; Henzinger, Monika H; Italiano, Giuseppe F. (42nd International Colloquium on Automata, Languages and Programming)
In this paper, we develop a dynamic version of the primal-dual method for optimization problems, and apply it to obtain the following results. (1) For the dynamic set-cover problem, we maintain an 𝑂(𝑓2)-approximately optimal solution in 𝑂(𝑓⋅log(𝑚+𝑛)) amortized update time, where 𝑓 is the maximum “frequency” of an element, 𝑛 is the number of sets, and 𝑚 is the maximum number of elements in the universe at any point in time. (2) For the dynamic 𝑏-matching problem, we maintain an 𝑂(1)-approximately optimal solution in 𝑂(log3𝑛) amortized update time, where 𝑛 is the number of nodes in the graph.

Split diversity in constrained conservation prioritization using integer linear programming - Chernomor, Olga; Minh, Bui Quang; Forest, Félix; Klaere, Steffen; Ingram, Travis; Henzinger, Monika H; von Haeseler, Arndt (Methods in Ecology and Evolution)
Phylogenetic diversity (PD) is a measure of biodiversity based on the evolutionary history of species. Here, we discuss several optimization problems related to the use of PD, and the more general measure split diversity (SD), in conservation prioritization. Depending on the conservation goal and the information available about species, one can construct optimization routines that incorporate various conservation constraints. We demonstrate how this information can be used to select sets of species for conservation action. Specifically, we discuss the use of species' geographic distributions, the choice of candidates under economic pressure, and the use of predator–prey interactions between the species in a community to define viability constraints. Despite such optimization problems falling into the area of NP hard problems, it is possible to solve them in a reasonable amount of time using integer programming. We apply integer linear programming to a variety of models for conservation prioritization that incorporate the SD measure. We exemplarily show the results for two data sets: the Cape region of South Africa and a Caribbean coral reef community. Finally, we provide user-friendly software at http://www.cibiv.at/software/pda.

Unifying and strengthening hardness for dynamic problems via the online matrix-vector multiplication conjecture - Henzinger, Monika H; Krinninger, Sebastian; Nanongkai, Danupon; Saranurak, Thatchaphol (47th Annual ACM Symposium on Theory of Computing)
Consider the following Online Boolean Matrix-Vector Multiplication problem: We are given an n x n matrix M and will receive n column-vectors of size n, denoted by v1, ..., vn, one by one. After seeing each vector vi, we have to output the product Mvi before we can see the next vector. A naive algorithm can solve this problem using O(n3) time in total, and its running time can be slightly improved to O(n3/log2 n) [Williams SODA'07]. We show that a conjecture that there is no truly subcubic (O(n3-ε)) time algorithm for this problem can be used to exhibit the underlying polynomial time hardness shared by many dynamic problems. For a number of problems, such as subgraph connectivity, Pagh's problem, d-failure connectivity, decremental single-source shortest paths, and decremental transitive closure, this conjecture implies tight hardness results. Thus, proving or disproving this conjecture will be very interesting as it will either imply several tight unconditional lower bounds or break through a common barrier that blocks progress with these problems. This conjecture might also be considered as strong evidence against any further improvement for these problems since refuting it will imply a major breakthrough for combinatorial Boolean matrix multiplication and other long-standing problems if the term "combinatorial algorithms" is interpreted as "Strassen-like algorithms" [Ballard et al. SPAA'11]. The conjecture also leads to hardness results for problems that were previously based on diverse problems and conjectures -- such as 3SUM, combinatorial Boolean matrix multiplication, triangle detection, and multiphase -- thus providing a uniform way to prove polynomial hardness results for dynamic algorithms; some of the new proofs are also simpler or even become trivial. The conjecture also leads to stronger and new, non-trivial, hardness results, e.g., for the fully-dynamic densest subgraph and diameter problems.

Space- and time-efficient algorithm for maintaining dense subgraphs on one-pass dynamic streams - Bhattacharya, Sayan; Henzinger, Monika H; Nanongkai, Danupon; Tsourakakis, Charalampos (47th Annual ACM Symposium on Theory of Computing)
While in many graph mining applications it is crucial to handle a stream of updates efficiently in terms of both time and space, not much was known about achieving such type of algorithm. In this paper we study this issue for a problem which lies at the core of many graph mining applications called densest subgraph problem. We develop an algorithm that achieves time- and space-efficiency for this problem simultaneously. It is one of the first of its kind for graph problems to the best of our knowledge. Given an input graph, the densest subgraph is the subgraph that maximizes the ratio between the number of edges and the number of nodes. For any ε>0, our algorithm can, with high probability, maintain a (4+ε)-approximate solution under edge insertions and deletions using ~O(n) space and ~O(1) amortized time per update; here, $n$ is the number of nodes in the graph and ~O hides the O(polylog_{1+ε} n) term. The approximation ratio can be improved to (2+ε) with more time. It can be extended to a (2+ε)-approximation sublinear-time algorithm and a distributed-streaming algorithm. Our algorithm is the first streaming algorithm that can maintain the densest subgraph in one pass. Prior to this, no algorithm could do so even in the special case of an incremental stream and even when there is no time restriction. The previously best algorithm in this setting required O(log n) passes [BahmaniKV12]. The space required by our algorithm is tight up to a polylogarithmic factor.

Welfare maximization with friends-of-friends network externalities - Bhattacharya, Sayan; Dvorák, Wolfgang; Henzinger, Monika H; Starnberger, Martin (32nd International Symposium on Theoretical Aspects of Computer Science)
Online social networks allow the collection of large amounts of data about the influence between users connected by a friendship-like relationship. When distributing items among agents forming a social network, this information allows us to exploit network externalities that each agent receives from his neighbors that get the same item. In this paper we consider Friends-of-Friends (2-hop) network externalities, i.e., externalities that not only depend on the neighbors that get the same item but also on neighbors of neighbors. For these externalities we study a setting where multiple different items are assigned to unit-demand agents. Specifically, we study the problem of welfare maximization under different types of externality functions. Let n be the number of agents and m be the number of items. Our contributions are the following: (1) We show that welfare maximization is APX-hard; we show that even for step functions with 2-hop (and also with 1-hop) externalities it is NP-hard to approximate social welfare better than (1-1/e). (2) On the positive side we present (i) an O(sqrt n)-approximation algorithm for general concave externality functions, (ii) an O(\log m)-approximation algorithm for linear externality functions, and (iii) an (1-1/e)\frac{1}{6}-approximation algorithm for 2-hop step function externalities. We also improve the result from [6] for 1-hop step function externalities by giving a (1-1/e)/2-approximation algorithm.

Truthful unit-demand auctions with budgets revisited - Henzinger, Monika H; Loitzenbauer, Veronika (Theoretical Computer Science)
We consider auctions of indivisible items to unit-demand bidders with budgets. This setting was suggested as an expressive model for single sponsored search auctions. Prior work presented mechanisms that compute bidder-optimal outcomes and are truthful for a restricted set of inputs, i.e., inputs in so-called general position. This condition is easily violated. We provide the first mechanism that is truthful in expectation for all inputs and achieves for each bidder no worse utility than the bidder-optimal outcome. Additionally we give a complete characterization for which inputs mechanisms that compute bidder-optimal outcomes are truthful.

Origami multistability: From single vertices to metasheets - Waitukaitis, Scott R; Menaut, Rémi; Chen, Bryan; Van Hecke, Martin (APS Physics, Physical Review Letters)
We show that the simplest building blocks of origami-based materials - rigid, degree-four vertices - are generically multistable. The existence of two distinct branches of folding motion emerging from the flat state suggests at least bistability, but we show how nonlinearities in the folding motions allow generic vertex geometries to have as many as five stable states. In special geometries with collinear folds and symmetry, more branches emerge leading to as many as six stable states. Tuning the fold energy parameters, we show how monostability is also possible. Finally, we show how to program the stability features of a single vertex into a periodic fold tessellation. The resulting metasheets provide a previously unanticipated functionality - tunable and switchable shape and size via multistability.

V-ATPase activity in the TGN/EE is required for exocytosis and recycling in Arabidopsis - Yu, Luo; Scholl, Stefan; Doering, Anett; Yi, Zhang; Irani, Niloufer; Di Rubbo, Simone; Neumetzler, Lutz; Krishnamoorthy, Praveen; Van Houtte, Isabelle; Mylle, Evelien; Bischoff, Volker; Vernhettes, Samantha; et al. (Nature Plants)
In plants, vacuolar H+-ATPase (V-ATPase) activity acidifies both the trans-Golgi network/early endosome (TGN/EE) and the vacuole. This dual V-ATPase function has impeded our understanding of how the pH homeostasis within the plant TGN/EE controls exo- and endocytosis. Here, we show that the weak V-ATPase mutant deetiolated3 (det3) displayed a pH increase in the TGN/EE, but not in the vacuole, strongly impairing secretion and recycling of the brassinosteroid receptor and the cellulose synthase complexes to the plasma membrane, in contrast to mutants lacking tonoplast-localized V-ATPase activity only. The brassinosteroid insensitivity and the cellulose deficiency defects in det3 were tightly correlated with reduced Golgi and TGN/EE motility. Thus, our results provide strong evidence that acidification of the TGN/EE, but not of the vacuole, is indispensable for functional secretion and recycling in plants.

Lifelong learning with non-i.i.d. tasks - Pentina, Anastasia; Lampert, Christoph
In this work we aim at extending the theoretical foundations of lifelong learning. Previous work analyzing this scenario is based on the assumption that learning tasks are sampled i.i.d. from a task environment or limited to strongly constrained data distributions. Instead, we study two scenarios when lifelong learning is possible, even though the observed tasks do not form an i.i.d. sample: first, when they are sampled from the same environment, but possibly with dependencies, and second, when the task environment is allowed to change over time in a consistent way. In the first case we prove a PAC-Bayesian theorem that can be seen as a direct generalization of the analogous previous result for the i.i.d. case. For the second scenario we propose to learn an inductive bias in form of a transfer procedure. We present a generalization bound and show on a toy example how it can be used to identify a beneficial transfer algorithm.

Statistical topological data analysis-A kernel perspective - Kwitt, Roland; Huber, Stefan; Niethammer, Marc; Lin, Weili; Bauer, Ulrich
We consider the problem of statistical computations with persistence diagrams, a summary representation of topological features in data. These diagrams encode persistent homology, a widely used invariant in topological data analysis. While several avenues towards a statistical treatment of the diagrams have been explored recently, we follow an alternative route that is motivated by the success of methods based on the embedding of probability measures into reproducing kernel Hilbert spaces. In fact, a positive definite kernel on persistence diagrams has recently been proposed, connecting persistent homology to popular kernel-based learning techniques such as support vector machines. However, important properties of that kernel enabling a principled use in the context of probability measure embeddings remain to be explored. Our contribution is to close this gap by proving universality of a variant of the original kernel, and to demonstrate its effective use in twosample hypothesis testing on synthetic as well as real-world data.

First steps towards a runtime comparison of natural and artificial evolution - Paixao, Tiago; Sudholt, Dirk; Heredia, Jorge; Trubenova, Barbora (Proceedings of the 2015 Annual Conference on Genetic and Evolutionary Computation)
Evolutionary algorithms (EAs) form a popular optimisation paradigm inspired by natural evolution. In recent years the field of evolutionary computation has developed a rigorous analytical theory to analyse their runtime on many illustrative problems. Here we apply this theory to a simple model of natural evolution. In the Strong Selection Weak Mutation (SSWM) evolutionary regime the time between occurrence of new mutations is much longer than the time it takes for a new beneficial mutation to take over the population. In this situation, the population only contains copies of one genotype and evolution can be modelled as a (1+1)-type process where the probability of accepting a new genotype (improvements or worsenings) depends on the change in fitness. We present an initial runtime analysis of SSWM, quantifying its performance for various parameters and investigating differences to the (1+1) EA. We show that SSWM can have a moderate advantage over the (1+1) EA at crossing fitness valleys and study an example where SSWM outperforms the (1+1) EA by taking advantage of information on the fitness gradient.

Policy privacy in cryptographic access control - Ferrara, Anna; Fuchsbauer, Georg; Liu, Bin; Warinschi, Bogdan
Cryptographic access control offers selective access to encrypted data via a combination of key management and functionality-rich cryptographic schemes, such as attribute-based encryption. Using this approach, publicly available meta-data may inadvertently leak information on the access policy that is enforced by cryptography, which renders cryptographic access control unusable in settings where this information is highly sensitive. We begin to address this problem by presenting rigorous definitions for policy privacy in cryptographic access control. For concreteness we set our results in the model of Role-Based Access Control (RBAC), where we identify and formalize several different flavors of privacy, however, our framework should serve as inspiration for other models of access control. Based on our insights we propose a new system which significantly improves on the privacy properties of state-of-the-art constructions. Our design is based on a novel type of privacy-preserving attribute-based encryption, which we introduce and show how to instantiate. We present our results in the context of a cryptographic RBAC system by Ferrara et al. (CSF'13), which uses cryptography to control read access to files, while write access is still delegated to trusted monitors. We give an extension of the construction that permits cryptographic control over write access. Our construction assumes that key management uses out-of-band channels between the policy enforcer and the users but eliminates completely the need for monitoring read/write access to the data.

Cohomology of large semiprojective hyperkähler varieties - Tamas Hausel; Rodríguez Villegas, Fernando (Asterisque)
In this paper we survey geometric and arithmetic techniques to study the cohomology of semiprojective hyperkähler manifolds including toric hyperkähler varieties, Nakajima quiver varieties and moduli spaces of Higgs bundles on Riemann surfaces. The resulting formulae for their Poincaré polynomials are combinatorial and representation theoretical in nature. In particular we will look at their Betti numbers and will establish some results and state some expectations on their asymptotic shape.

A stable multi-scale kernel for topological machine learning - Reininghaus, Jan; Huber, Stefan; Bauer, Ulrich; Kwitt, Roland
Topological data analysis offers a rich source of valuable information to study vision problems. Yet, so far we lack a theoretically sound connection to popular kernel-based learning techniques, such as kernel SVMs or kernel PCA. In this work, we establish such a connection by designing a multi-scale kernel for persistence diagrams, a stable summary representation of topological features in data. We show that this kernel is positive definite and prove its stability with respect to the 1-Wasserstein distance. Experiments on two benchmark datasets for 3D shape classification/retrieval and texture recognition show considerable performance gains of the proposed method compared to an alternative approach that is based on the recently introduced persistence landscapes.

The need for language support for fault-tolerant distributed systems - Dragoi, Cezara; Henzinger, Thomas A; Zufferey, Damien
Fault-tolerant distributed algorithms play an important role in many critical/high-availability applications. These algorithms are notoriously difficult to implement correctly, due to asynchronous communication and the occurrence of faults, such as the network dropping messages or computers crashing. Nonetheless there is surprisingly little language and verification support to build distributed systems based on fault-tolerant algorithms. In this paper, we present some of the challenges that a designer has to overcome to implement a fault-tolerant distributed system. Then we review different models that have been proposed to reason about distributed algorithms and sketch how such a model can form the basis for a domain-specific programming language. Adopting a high-level programming model can simplify the programmer's life and make the code amenable to automated verification, while still compiling to efficiently executable code. We conclude by summarizing the current status of an ongoing language design and implementation project that is based on this idea.

Allelome.PRO, a pipeline to define allele-specific genomic features from high-throughput sequencing data - Andergassen, Daniel; Dotter, Christoph; Kulinski, Tomasz; Guenzl, Philipp; Bammer, Philipp; Barlow, Denise; Pauler, Florian; Hudson, Quanah (Nucleic Acids Research)
Detecting allelic biases from high-throughput sequencing data requires an approach that maximises sensitivity while minimizing false positives. Here, we present Allelome.PRO, an automated user-friendly bioinformatics pipeline, which uses high-throughput sequencing data from reciprocal crosses of two genetically distinct mouse strains to detect allele-specific expression and chromatin modifications. Allelome.PRO extends approaches used in previous studies that exclusively analyzed imprinted expression to give a complete picture of the ‘allelome’ by automatically categorising the allelic expression of all genes in a given cell type into imprinted, strain-biased, biallelic or non-informative. Allelome.PRO offers increased sensitivity to analyze lowly expressed transcripts, together with a robust false discovery rate empirically calculated from variation in the sequencing data. We used RNA-seq data from mouse embryonic fibroblasts from F1 reciprocal crosses to determine a biologically relevant allelic ratio cutoff, and define for the first time an entire allelome. Furthermore, we show that Allelome.PRO detects differential enrichment of H3K4me3 over promoters from ChIP-seq data validating the RNA-seq results. This approach can be easily extended to analyze histone marks of active enhancers, or transcription factor binding sites and therefore provides a powerful tool to identify candidate cis regulatory elements genome wide.

Polynomial time decidability of weighted synchronization under partial observability - Kretinsky, Jan; Larsen, Kim; Laursen, Simon; Srba, Jiří
We consider weighted automata with both positive and negative integer weights on edges and study the problem of synchronization using adaptive strategies that may only observe whether the current weight-level is negative or nonnegative. We show that the synchronization problem is decidable in polynomial time for deterministic weighted automata.

Relaxed disk packing - Edelsbrunner, Herbert; Iglesias Ham, Mabel; Kurlin, Vitaliy (Proceedings of the 27th Canadian Conference on Computational Geometry)
Motivated by biological questions, we study configurations of equal-sized disks in the Euclidean plane that neither pack nor cover. Measuring the quality by the probability that a random point lies in exactly one disk, we show that the regular hexagonal grid gives the maximum among lattice configurations.

Spectral statistics of large dimensional spearman s rank correlation matrix and its application - Bao, Zhigang; Lin, Liang; Pan, Guangming; Zhou, Wang (Annals of Statistics)
Let Q = (Q1, . . . , Qn) be a random vector drawn from the uniform distribution on the set of all n! permutations of {1, 2, . . . , n}. Let Z = (Z1, . . . , Zn), where Zj is the mean zero variance one random variable obtained by centralizing and normalizing Qj , j = 1, . . . , n. Assume that Xi , i = 1, . . . ,p are i.i.d. copies of 1/√ p Z and X = Xp,n is the p × n random matrix with Xi as its ith row. Then Sn = XX is called the p × n Spearman's rank correlation matrix which can be regarded as a high dimensional extension of the classical nonparametric statistic Spearman's rank correlation coefficient between two independent random variables. In this paper, we establish a CLT for the linear spectral statistics of this nonparametric random matrix model in the scenario of high dimension, namely, p = p(n) and p/n→c ∈ (0,∞) as n→∞.We propose a novel evaluation scheme to estimate the core quantity in Anderson and Zeitouni's cumulant method in [Ann. Statist. 36 (2008) 2553-2576] to bypass the so-called joint cumulant summability. In addition, we raise a two-step comparison approach to obtain the explicit formulae for the mean and covariance functions in the CLT. Relying on this CLT, we then construct a distribution-free statistic to test complete independence for components of random vectors. Owing to the nonparametric property, we can use this test on generally distributed random variables including the heavy-tailed ones.

A Herman-Avila-Bochi formula for higher-dimensional pseudo-unitary and Hermitian-symplectic-cocycles - Sadel, Christian (Ergodic Theory and Dynamical Systems)
A Herman-Avila-Bochi type formula is obtained for the average sum of the top d Lyapunov exponents over a one-parameter family of double-struck G-cocycles, where double-struck G is the group that leaves a certain, non-degenerate Hermitian form of signature (c, d) invariant. The generic example of such a group is the pseudo-unitary group U(c, d) or, in the case c = d, the Hermitian-symplectic group HSp(2d) which naturally appears for cocycles related to Schrödinger operators. In the case d = 1, the formula for HSp(2d) cocycles reduces to the Herman-Avila-Bochi formula for SL(2, ℝ) cocycles.

On computability and triviality of well groups - Franek, Peter; Krcál, Marek
The concept of well group in a special but important case captures homological properties of the zero set of a continuous map f from K to R^n on a compact space K that are invariant with respect to perturbations of f. The perturbations are arbitrary continuous maps within L_infty distance r from f for a given r > 0. The main drawback of the approach is that the computability of well groups was shown only when dim K = n or n = 1. Our contribution to the theory of well groups is twofold: on the one hand we improve on the computability issue, but on the other hand we present a range of examples where the well groups are incomplete invariants, that is, fail to capture certain important robust properties of the zero set. For the first part, we identify a computable subgroup of the well group that is obtained by cap product with the pullback of the orientation of R^n by f. In other words, well groups can be algorithmically approximated from below. When f is smooth and dim K < 2n-2, our approximation of the (dim K-n)th well group is exact. For the second part, we find examples of maps f, f' from K to R^n with all well groups isomorphic but whose perturbations have different zero sets. We discuss on a possible replacement of the well groups of vector valued maps by an invariant of a better descriptive power and computability status.

Universality for the largest eigenvalue of sample covariance matrices with general population - Bao, Zhigang; Pan, Guangming; Zhou, Wang (Annals of Statistics)
This paper is aimed at deriving the universality of the largest eigenvalue of a class of high-dimensional real or complex sample covariance matrices of the form W N =Σ 1/2XX∗Σ 1/2 . Here, X = (xij )M,N is an M× N random matrix with independent entries xij , 1 ≤ i M,≤ 1 ≤ j ≤ N such that Exij = 0, E|xij |2 = 1/N . On dimensionality, we assume that M = M(N) and N/M → d ε (0, ∞) as N ∞→. For a class of general deterministic positive-definite M × M matrices Σ , under some additional assumptions on the distribution of xij 's, we show that the limiting behavior of the largest eigenvalue of W N is universal, via pursuing a Green function comparison strategy raised in [Probab. Theory Related Fields 154 (2012) 341-407, Adv. Math. 229 (2012) 1435-1515] by Erd″os, Yau and Yin for Wigner matrices and extended by Pillai and Yin [Ann. Appl. Probab. 24 (2014) 935-1001] to sample covariance matrices in the null case (&Epsi = I ). Consequently, in the standard complex case (Ex2 ij = 0), combing this universality property and the results known for Gaussian matrices obtained by El Karoui in [Ann. Probab. 35 (2007) 663-714] (nonsingular case) and Onatski in [Ann. Appl. Probab. 18 (2008) 470-490] (singular case), we show that after an appropriate normalization the largest eigenvalue of W N converges weakly to the type 2 Tracy-Widom distribution TW2 . Moreover, in the real case, we show that whenΣ is spiked with a fixed number of subcritical spikes, the type 1 Tracy-Widom limit TW1 holds for the normalized largest eigenvalue of W N , which extends a result of Féral and Péché in [J. Math. Phys. 50 (2009) 073302] to the scenario of nondiagonal Σ and more generally distributed X . In summary, we establish the Tracy-Widom type universality for the largest eigenvalue of generally distributed sample covariance matrices under quite light assumptions on &Sigma . Applications of these limiting results to statistical signal detection and structure recognition of separable covariance matrices are also discussed.

Gap universality of generalized Wigner and β ensembles - Erdös, László; Yau, Horng (Journal of the European Mathematical Society)
We consider generalized Wigner ensembles and general β-ensembles with analytic potentials for any β ≥ 1. The recent universality results in particular assert that the local averages of consecutive eigenvalue gaps in the bulk of the spectrum are universal in the sense that they coincide with those of the corresponding Gaussian β-ensembles. In this article, we show that local averaging is not necessary for this result, i.e. we prove that the single gap distributions in the bulk are universal. In fact, with an additional step, our result can be extended to any C4(ℝ) potential.

The logarithmic law of random determinant - Bao, Zhigang; Pan, Guangming; Zhou, Wang (Bernoulli)
Consider the square random matrix An = (aij)n,n, where {aij:= a(n)ij , i, j = 1, . . . , n} is a collection of independent real random variables with means zero and variances one. Under the additional moment condition supn max1≤i,j ≤n Ea4ij <∞, we prove Girko's logarithmic law of det An in the sense that as n→∞ log | detAn| ? (1/2) log(n-1)! d/→√(1/2) log n N(0, 1).

The X chromosome of hemipteran insects: Conservation, dosage compensation and sex-biased expression - Pal, Arka; Vicoso, Beatriz (Genome Biology and Evolution)
Insects of the order Hemiptera (true bugs) use a wide range of mechanisms of sex determination, including genetic sex determination, paternal genome elimination, and haplodiploidy. Genetic sex determination, the prevalent mode, is generally controlled by a pair of XY sex chromosomes or by an XX/X0 system, but different configurations that include additional sex chromosomes are also present. Although this diversity of sex determining systems has been extensively studied at the cytogenetic level, only the X chromosome of the model pea aphid Acyrthosiphon pisum has been analyzed at the genomic level, and little is known about X chromosome biology in the rest of the order. In this study, we take advantage of published DNA- and RNA-seq data from three additional Hemiptera species to perform a comparative analysis of the gene content and expression of the X chromosome throughout this clade. We find that, despite showing evidence of dosage compensation, the X chromosomes of these species show female-biased expression, and a deficit of male-biased genes, in direct contrast to the pea aphid X. We further detect an excess of shared gene content between these very distant species, suggesting that despite the diversity of sex determining systems, the same chromosomal element is used as the X throughout a large portion of the order.

From large deviations to Wasserstein gradient flows in multiple dimensions - Erbar, Matthias; Maas, Jan; Renger, Michiel (Electronic Communications in Probability)
We study the large deviation rate functional for the empirical distribution of independent Brownian particles with drift. In one dimension, it has been shown by Adams, Dirr, Peletier and Zimmer that this functional is asymptotically equivalent (in the sense of Γ-convergence) to the Jordan-Kinderlehrer-Otto functional arising in the Wasserstein gradient flow structure of the Fokker-Planck equation. In higher dimensions, part of this statement (the lower bound) has been recently proved by Duong, Laschos and Renger, but the upper bound remained open, since the proof of Duong et al relies on regularity properties of optimal transport maps that are restricted to one dimension. In this note we present a new proof of the upper bound, thereby generalising the result of Adams et al to arbitrary dimensions.

The interpretation of selection coefficients - Barton, Nicholas H; Servedio, Maria (Evolution)
Evolutionary biologists have an array of powerful theoretical techniques that can accurately predict changes in the genetic composition of populations. Changes in gene frequencies and genetic associations between loci can be tracked as they respond to a wide variety of evolutionary forces. However, it is often less clear how to decompose these various forces into components that accurately reflect the underlying biology. Here, we present several issues that arise in the definition and interpretation of selection and selection coefficients, focusing on insights gained through the examination of selection coefficients in multilocus notation. Using this notation, we discuss how its flexibility-which allows different biological units to be identified as targets of selection-is reflected in the interpretation of the coefficients that the notation generates. In many situations, it can be difficult to agree on whether loci can be considered to be under "direct" versus "indirect" selection, or to quantify this selection. We present arguments for what the terms direct and indirect selection might best encompass, considering a range of issues, from viability and sexual selection to kin selection. We show how multilocus notation can discriminate between direct and indirect selection, and describe when it can do so.

Arbeitsgruppe „Nationale Strategie“ des Open Access Network Austria OANA - Bauer, Bruno; Blechl, Guido; Bock, Christoph; Danowski, Patrick; Ferus, Andreas; Graschopf, Anton; König, Thomas; Mayer, Katja; Reckling, Falk; Rieck, Katharina; Seitz, Peter; Stöger, Herwig; et al. (VÖB Mitteilungen)
Based on 16 recommendations, efforts should be made to achieve the following goal: By 2025, all scholarly publication activity in Austria should be Open Access. In other words, the final versions of all scholarly publications resulting from the support of public resources must be freely accessible on the Internet without delay (Gold Open Access). The resources required to meet this obligation shall be provided to the authors, or the cost of the publication venues shall be borne directly by the research organisations.

Minimal moment equations for stochastic models of biochemical reaction networks with partially finite state space - Ruess, Jakob (Journal of Chemical Physics)
Many stochastic models of biochemical reaction networks contain some chemical species for which the number of molecules that are present in the system can only be finite (for instance due to conservation laws), but also other species that can be present in arbitrarily large amounts. The prime example of such networks are models of gene expression, which typically contain a small and finite number of possible states for the promoter but an infinite number of possible states for the amount of mRNA and protein. One of the main approaches to analyze such models is through the use of equations for the time evolution of moments of the chemical species. Recently, a new approach based on conditional moments of the species with infinite state space given all the different possible states of the finite species has been proposed. It was argued that this approach allows one to capture more details about the full underlying probability distribution with a smaller number of equations. Here, I show that the result that less moments provide more information can only stem from an unnecessarily complicated description of the system in the classical formulation. The foundation of this argument will be the derivation of moment equations that describe the complete probability distribution over the finite state space but only low-order moments over the infinite state space. I will show that the number of equations that is needed is always less than what was previously claimed and always less than the number of conditional moment equations up to the same order. To support these arguments, a symbolic algorithm is provided that can be used to derive minimal systems of unconditional moment equations for models with partially finite state space.

Transcriptional regulation of PIN genes by FOUR LIPS and MYB88 during Arabidopsis root gravitropism - Wang, Hongzhe; Yang, Kezhen; Zou, Junjie; Zhu, Lingling; Xie, Zidian; Morita, Miyoterao; Tasaka, Masao; Friml, Jirí; Grotewold, Erich; Beeckman, Tom; Vanneste, Steffen; Sack, Fred; et al. (Nature Communications)
PIN proteins are auxin export carriers that direct intercellular auxin flow and in turn regulate many aspects of plant growth and development including responses to environmental changes. The Arabidopsis R2R3-MYB transcription factor FOUR LIPS (FLP) and its paralogue MYB88 regulate terminal divisions during stomatal development, as well as female reproductive development and stress responses. Here we show that FLP and MYB88 act redundantly but differentially in regulating the transcription of PIN3 and PIN7 in gravity-sensing cells of primary and lateral roots. On the one hand, FLP is involved in responses to gravity stimulation in primary roots, whereas on the other, FLP and MYB88 function complementarily in establishing the gravitropic set-point angles of lateral roots. Our results support a model in which FLP and MYB88 expression specifically determines the temporal-spatial patterns of PIN3 and PIN7 transcription that are closely associated with their preferential functions during root responses to gravity.

Iterative experiment design guides the characterization of a light-inducible gene expression circuit - Ruess, Jakob; Parise, Francesca; Milias Argeitis, Andreas; Khammash, Mustafa; Lygeros, John (PNAS)
Systems biology rests on the idea that biological complexity can be better unraveled through the interplay of modeling and experimentation. However, the success of this approach depends critically on the informativeness of the chosen experiments, which is usually unknown a priori. Here, we propose a systematic scheme based on iterations of optimal experiment design, flow cytometry experiments, and Bayesian parameter inference to guide the discovery process in the case of stochastic biochemical reaction networks. To illustrate the benefit of our methodology, we apply it to the characterization of an engineered light-inducible gene expression circuit in yeast and compare the performance of the resulting model with models identified from nonoptimal experiments. In particular, we compare the parameter posterior distributions and the precision to which the outcome of future experiments can be predicted. Moreover, we illustrate how the identified stochastic model can be used to determine light induction patterns that make either the average amount of protein or the variability in a population of cells follow a desired profile. Our results show that optimal experiment design allows one to derive models that are accurate enough to precisely predict and regulate the protein expression in heterogeneous cell populations over extended periods of time.

Cav1.3 channels as key regulators of neuron-like firings and catecholamine release in chromaffin cells - Vandael, David H; Marcantoni, Andrea; Carbone, Emilio (Current Molecular Pharmacology)
Neuronal and neuroendocrine L-type calcium channels (Cav1.2, Cav1.3) open readily at relatively low membrane potentials and allow Ca2+ to enter the cells near resting potentials. In this way, Cav1.2 and Cav1.3 shape the action potential waveform, contribute to gene expression, synaptic plasticity, neuronal differentiation, hormone secretion and pacemaker activity. In the chromaffin cells (CCs) of the adrenal medulla, Cav1.3 is highly expressed and is shown to support most of the pacemaking current that sustains action potential (AP) firings and part of the catecholamine secretion. Cav1.3 forms Ca2+-nanodomains with the fast inactivating BK channels and drives the resting SK currents. These latter set the inter-spike interval duration between consecutive spikes during spontaneous firing and the rate of spike adaptation during sustained depolarizations. Cav1.3 plays also a primary role in the switch from “tonic” to “burst” firing that occurs in mouse CCs when either the availability of voltage-gated Na channels (Nav) is reduced or the β2 subunit featuring the fast inactivating BK channels is deleted. Here, we discuss the functional role of these “neuronlike” firing modes in CCs and how Cav1.3 contributes to them. The open issue is to understand how these novel firing patterns are adapted to regulate the quantity of circulating catecholamines during resting condition or in response to acute and chronic stress.

Toward a unifying framework for evolutionary processes - Paixao, Tiago; Badkobeh, Golnaz; Barton, Nicholas H; Çörüş, Doğan; Dang, Duccuong; Friedrich, Tobias; Lehre, Per; Sudholt, Dirk; Sutton, Andrew; Trubenova, Barbora (Journal of Theoretical Biology)
The theory of population genetics and evolutionary computation have been evolving separately for nearly 30 years. Many results have been independently obtained in both fields and many others are unique to its respective field. We aim to bridge this gap by developing a unifying framework for evolutionary processes that allows both evolutionary algorithms and population genetics models to be cast in the same formal framework. The framework we present here decomposes the evolutionary process into its several components in order to facilitate the identification of similarities between different models. In particular, we propose a classification of evolutionary operators based on the defining properties of the different components. We cast several commonly used operators from both fields into this common framework. Using this, we map different evolutionary and genetic algorithms to different evolutionary regimes and identify candidates with the most potential for the translation of results between the fields. This provides a unified description of evolutionary processes and represents a stepping stone towards new tools and results to both fields.

Nanoscale distribution of presynaptic Ca2+ channels and its impact on vesicular release during development - Nakamura, Yukihiro; Harada, Harumi; Kamasawa, Naomi; Matsui, Ko; Rothman, Jason; Shigemoto, Ryuichi; Silver, R Angus; Digregorio, David; Takahashi, Tomoyuki (Neuron)
Synaptic efficacy and precision are influenced by the coupling of voltage-gated Ca2+ channels (VGCCs) to vesicles. But because the topography of VGCCs and their proximity to vesicles is unknown, a quantitative understanding of the determinants of vesicular release at nanometer scale is lacking. To investigate this, we combined freeze-fracture replica immunogold labeling of Cav2.1 channels, local [Ca2+] imaging, and patch pipette perfusion of EGTA at the calyx of Held. Between postnatal day 7 and 21, VGCCs formed variable sized clusters and vesicular release became less sensitive to EGTA, whereas fixed Ca2+ buffer properties remained constant. Experimentally constrained reaction-diffusion simulations suggest that Ca2+ sensors for vesicular release are located at the perimeter of VGCC clusters (<30nm) and predict that VGCC number per cluster determines vesicular release probability without altering release time course. This "perimeter release model" provides a unifying framework accounting for developmental changes in both synaptic efficacy and time course.

Using supported bilayers to study the spatiotemporal organization of membrane-bound proteins - Nguyen, Phuong; Field, Christine; Groen, Aaron; Mitchison, Timothy; Loose, Martin (Building a Cell from its Components Parts)
Cell division in prokaryotes and eukaryotes is commonly initiated by the well-controlled binding of proteins to the cytoplasmic side of the cell membrane. However, a precise characterization of the spatiotemporal dynamics of membrane-bound proteins is often difficult to achieve in vivo. Here, we present protocols for the use of supported lipid bilayers to rebuild the cytokinetic machineries of cells with greatly different dimensions: the bacterium Escherichia coli and eggs of the vertebrate Xenopus laevis. Combined with total internal reflection fluorescence microscopy, these experimental setups allow for precise quantitative analyses of membrane-bound proteins. The protocols described to obtain glass-supported membranes from bacterial and vertebrate lipids can be used as starting points for other reconstitution experiments. We believe that similar biochemical assays will be instrumental to study the biochemistry and biophysics underlying a variety of complex cellular tasks, such as signaling, vesicle trafficking, and cell motility.

Host–pathogen coevolution: The selective advantage of Bacillus thuringiensis virulence and its cry toxin genes - El Masri, Leila; Branca, Antoine; Sheppard, Anna; Papkou, Andrei; Laehnemann, David; Guenther, Patrick; Prahl, Swantje; Saebelfeld, Manja; Hollensteiner, Jacqueline; Liesegang, Heiko; Brzuszkiewicz, Elzbieta; Daniel, Rolf; et al. (PLoS Biology)
Reciprocal coevolution between host and pathogen is widely seen as a major driver of evolution and biological innovation. Yet, to date, the underlying genetic mechanisms and associated trait functions that are unique to rapid coevolutionary change are generally unknown. We here combined experimental evolution of the bacterial biocontrol agent Bacillus thuringiensis and its nematode host Caenorhabditis elegans with large-scale phenotyping, whole genome analysis, and functional genetics to demonstrate the selective benefit of pathogen virulence and the underlying toxin genes during the adaptation process. We show that: (i) high virulence was specifically favoured during pathogen–host coevolution rather than pathogen one-sided adaptation to a nonchanging host or to an environment without host; (ii) the pathogen genotype BT-679 with known nematocidal toxin genes and high virulence specifically swept to fixation in all of the independent replicate populations under coevolution but only some under one-sided adaptation; (iii) high virulence in the BT-679-dominated populations correlated with elevated copy numbers of the plasmid containing the nematocidal toxin genes; (iv) loss of virulence in a toxin-plasmid lacking BT-679 isolate was reconstituted by genetic reintroduction or external addition of the toxins.We conclude that sustained coevolution is distinct from unidirectional selection in shaping the pathogen's genome and life history characteristics. To our knowledge, this study is the first to characterize the pathogen genes involved in coevolutionary adaptation in an animal host–pathogen interaction system.

Flipping the photoswitch: Ion channels under light control - Mckenzie, Catherine; Sanchez Romero, Inmaculada; Janovjak, Harald L (Novel chemical tools to study ion channel biology)
Nature has incorporated small photochromic molecules, colloquially termed 'photoswitches', in photoreceptor proteins to sense optical cues in photo-taxis and vision. While Nature's ability to employ light-responsive functionalities has long been recognized, it was not until recently that scientists designed, synthesized and applied synthetic photochromes to manipulate many of which open rapidly and locally in their native cell types, biological processes with the temporal and spatial resolution of light. Ion channels in particular have come to the forefront of proteins that can be put under the designer control of synthetic photochromes. Photochromic ion channel controllers are comprised of three classes, photochromic soluble ligands (PCLs), photochromic tethered ligands (PTLs) and photochromic crosslinkers (PXs), and in each class ion channel functionality is controlled through reversible changes in photochrome structure. By acting as light-dependent ion channel agonists, antagonist or modulators, photochromic controllers effectively converted a wide range of ion channels, including voltage-gated ion channels, 'leak channels', tri-, tetra- and pentameric ligand-gated ion channels, and temperaturesensitive ion channels, into man-made photoreceptors. Control by photochromes can be reversible, unlike in the case of 'caged' compounds, and non-invasive with high spatial precision, unlike pharmacology and electrical manipulation. Here, we introduce design principles of emerging photochromic molecules that act on ion channels and discuss the impact that these molecules are beginning to have on ion channel biophysics and neuronal physiology.

Infection of Tribolium castaneum with Bacillus thuringiensis: Quantification of bacterial replication within cadavers, transmission via cannibalism, and inhibition of spore germination - Milutinovic, Barbara; Höfling, Christina; Futo, Momir; Scharsack, Jörn; Kurtz, Joachim (Applied and Environmental Microbiology)
Reproduction within a host and transmission to the next host are crucial for the virulence and fitness of pathogens. Nevertheless, basic knowledge about such parameters is often missing from the literature, even for well-studied bacteria, such as Bacillus thuringiensis, an endospore-forming insect pathogen, which infects its hosts via the oral route. To characterize bacterial replication success, we made use of an experimental oral infection system for the red flour beetle Tribolium castaneum and developed a flow cytometric assay for the quantification of both spore ingestion by the individual beetle larvae and the resulting spore load after bacterial replication and resporulation within cadavers. On average, spore numbers increased 460-fold, showing that Bacillus thuringiensis grows and replicates successfully in insect cadavers. By inoculating cadaver-derived spores and spores from bacterial stock cultures into nutrient medium, we next investigated outgrowth characteristics of vegetative cells and found that cadaver- derived bacteria showed reduced growth compared to bacteria from the stock cultures. Interestingly, this reduced growth was a consequence of inhibited spore germination, probably originating from the host and resulting in reduced host mortality in subsequent infections by cadaver-derived spores. Nevertheless, we further showed that Bacillus thuringiensis transmission was possible via larval cannibalism when no other food was offered. These results contribute to our understanding of the ecology of Bacillus thuringiensis as an insect pathogen.

Clonally related forebrain interneurons disperse broadly across both functional areas and structural boundaries - Mayer, Christian; Jaglin, Xavier; Cobbs, Lucy; Bandler, Rachel; Streicher, Carmen; Cepko, Constance; Hippenmeyer, Simon; Fishell, Gord (Neuron)
The medial ganglionic eminence (MGE) gives rise to the majority of mouse forebrain interneurons. Here, we examine the lineage relationship among MGE-derived interneurons using a replication-defective retroviral library containing a highly diverse set of DNA barcodes. Recovering the barcodes from the mature progeny of infected progenitor cells enabled us to unambiguously determine their respective lineal relationship. We found that clonal dispersion occurs across large areas of the brain and is not restricted by anatomical divisions. As such, sibling interneurons can populate the cortex, hippocampus striatum, and globus pallidus. The majority of interneurons appeared to be generated from asymmetric divisions of MGE progenitor cells, followed by symmetric divisions within the subventricular zone. Altogether, our findings uncover that lineage relationships do not appear to determine interneuron allocation to particular regions. As such, it is likely that clonally related interneurons have considerable flexibility as to the particular forebrain circuits to which they can contribute.

Resolution of unmixed bipartite graphs - Mohammadi, Fatemeh; Moradi, Somayeh (Bulletin of the Korean Mathematical Society)
Let G be a graph on the vertex set V(G) = {x1,…,xn} with the edge set E(G), and let R = K[x1,…, xn] be the polynomial ring over a field K. Two monomial ideals are associated to G, the edge ideal I(G) generated by all monomials xixj with {xi,xj} ∈ E(G), and the vertex cover ideal IG generated by monomials ∏xi∈Cxi for all minimal vertex covers C of G. A minimal vertex cover of G is a subset C ⊂ V(G) such that each edge has at least one vertex in C and no proper subset of C has the same property. Indeed, the vertex cover ideal of G is the Alexander dual of the edge ideal of G. In this paper, for an unmixed bipartite graph G we consider the lattice of vertex covers LG and we explicitly describe the minimal free resolution of the ideal associated to LG which is exactly the vertex cover ideal of G. Then we compute depth, projective dimension, regularity and extremal Betti numbers of R/I(G) in terms of the associated lattice.

The Arabidopsis thaliana elongator complex subunit 2 epigenetically affects root development - Jia, Yuebin; Tian, Huiyu; Li, Hongjiang; Yu, Qianqian; Wang, Lei; Friml, Jirí; Ding, Zhaojun (Journal of Experimental Botany)
The elongator complex subunit 2 (ELP2) protein, one subunit of an evolutionarily conserved histone acetyltransferase complex, has been shown to participate in leaf patterning, plant immune and abiotic stress responses in Arabidopsis thaliana. Here, its role in root development was explored. Compared to the wild type, the elp2 mutant exhibited an accelerated differentiation of its root stem cells and cell division was more active in its quiescent centre (QC). The key transcription factors responsible for maintaining root stem cell and QC identity, such as AP2 transcription factors PLT1 (PLETHORA1) and PLT2 (PLETHORA2), GRAS transcription factors such as SCR (SCARECROW) and SHR (SHORT ROOT) and WUSCHEL-RELATED HOMEOBOX5 transcription factor WOX5, were all strongly down-regulated in the mutant. On the other hand, expression of the G2/M transition activator CYCB1 was substantially induced in elp2. The auxin efflux transporters PIN1 and PIN2 showed decreased protein levels and PIN1 also displayed mild polarity alterations in elp2, which resulted in a reduced auxin content in the root tip. Either the acetylation or methylation level of each of these genes differed between the mutant and the wild type, suggesting that the ELP2 regulation of root development involves the epigenetic modification of a range of transcription factors and other developmental regulators.

Rich bifurcation structure in a two patch vaccination model - Knipl, Diána; Pilarczyk, Pawel; Röst, Gergely (SIAM Journal on Applied Dynamical Systems)
We show that incorporating spatial dispersal of individuals into a simple vaccination epidemic model may give rise to a model that exhibits rich dynamical behavior. Using an SIVS (susceptible-infected-vaccinated-susceptible) model as a basis, we describe the spread of an infectious disease in a population split into two regions. In each subpopulation, both forward and backward bifurcations can occur. This implies that for disconnected regions the two-patch system may admit several steady states. We consider traveling between the regions and investigate the impact of spatial dispersal of individuals on the model dynamics. We establish conditions for the existence of multiple nontrivial steady states in the system, and we study the structure of the equilibria. The mathematical analysis reveals an unusually rich dynamical behavior, not normally found in the simple epidemic models. In addition to the disease-free equilibrium, eight endemic equilibria emerge from backward transcritical and saddle-node bifurcation points, forming an interesting bifurcation diagram. Stability of steady states, their bifurcations, and the global dynamics are investigated with analytical tools, numerical simulations, and rigorous set-oriented numerical computations.

Computational complexity of ecological and evolutionary spatial dynamics - Ibsen-Jensen, Rasmus; Chatterjee, Krishnendu; Nowak, Martin (PNAS)
There are deep, yet largely unexplored, connections between computer science and biology. Both disciplines examine how information proliferates in time and space. Central results in computer science describe the complexity of algorithms that solve certain classes of problems. An algorithm is deemed efficient if it can solve a problem in polynomial time, which means the running time of the algorithm is a polynomial function of the length of the input. There are classes of harder problems for which the fastest possible algorithm requires exponential time. Another criterion is the space requirement of the algorithm. There is a crucial distinction between algorithms that can find a solution, verify a solution, or list several distinct solutions in given time and space. The complexity hierarchy that is generated in this way is the foundation of theoretical computer science. Precise complexity results can be notoriously difficult. The famous question whether polynomial time equals nondeterministic polynomial time (i.e., P = NP) is one of the hardest open problems in computer science and all of mathematics. Here, we consider simple processes of ecological and evolutionary spatial dynamics. The basic question is: What is the probability that a new invader (or a new mutant)will take over a resident population?We derive precise complexity results for a variety of scenarios. We therefore show that some fundamental questions in this area cannot be answered by simple equations (assuming that P is not equal to NP).

Reporters for sensitive and quantitative measurement of auxin response - Liao, Cheyang; Smet, Wouter; Brunoud, Géraldine; Yoshida, Saiko; Vernoux, Teva; Weijers, Dolf (Nature Methods)
The visualization of hormonal signaling input and output is key to understanding how multicellular development is regulated. The plant signaling molecule auxin triggers many growth and developmental responses, but current tools lack the sensitivity or precision to visualize these. We developed a set of fluorescent reporters that allow sensitive and semiquantitative readout of auxin responses at cellular resolution in Arabidopsis thaliana. These generic tools are suitable for any transformable plant species.

Dual action of leptin on rest-firing and stimulated catecholamine release via phosphoinositide 3-kinase-riven BK channel up-regulation in mouse chromaffin cells - Gavello, Daniela; Vandael, David H; Gosso, Sara; Carbone, Emilio; Carabelli, Valentina (Journal of Physiology)
Leptin is an adipokine produced by the adipose tissue regulating body weight through its appetite-suppressing effect. Besides being expressed in the hypothalamus and hippocampus, leptin receptors (ObRs) are also present in chromaffin cells of the adrenal medulla. In the present study, we report the effect of leptin on mouse chromaffin cell (MCC) functionality, focusing on cell excitability and catecholamine secretion. Acute application of leptin (1 nm) on spontaneously firing MCCs caused a slowly developing membrane hyperpolarization followed by complete blockade of action potential (AP) firing. This inhibitory effect at rest was abolished by the BK channel blocker paxilline (1 μm), suggesting the involvement of BK potassium channels. Single-channel recordings in 'perforated microvesicles' confirmed that leptin increased BK channel open probability without altering its unitary conductance. BK channel up-regulation was associated with the phosphoinositide 3-kinase (PI3K) signalling cascade because the PI3K specific inhibitor wortmannin (100 nm) fully prevented BK current increase. We also tested the effect of leptin on evoked AP firing and Ca2+-driven exocytosis. Although leptin preserves well-adapted AP trains of lower frequency, APs are broader and depolarization-evoked exocytosis is increased as a result of the larger size of the ready-releasable pool and higher frequency of vesicle release. The kinetics and quantal size of single secretory events remained unaltered. Leptin had no effect on firing and secretion in db-/db- mice lacking the ObR gene, confirming its specificity. In conclusion, leptin exhibits a dual action on MCC activity. It dampens AP firing at rest but preserves AP firing and increases catecholamine secretion during sustained stimulation, highlighting the importance of the adipo-adrenal axis in the leptin-mediated increase of sympathetic tone and catecholamine release.

Editorial: Emergent neural computation from the interaction of different forms of plasticity - Gilson, Matthieu; Savin, Cristina; Zenke, Friedemann (Frontiers in Computational Neuroscience)

A coherent transcriptional feed-forward motif model for mediating auxin-sensitive PIN3 expression during lateral root development - Chen, Qian; Liu, Yang; Maere, Steven; Lee, Eunkyoung; Van Isterdael, Gert; Xie, Zidian; Xuan, Wei; Lucas, Jessica; Vassileva, Valya; Kitakura, Saeko; Marhavy, Peter; Wabnik, Krzysztof T; et al. (Nature Communications)
Multiple plant developmental processes, such as lateral root development, depend on auxin distribution patterns that are in part generated by the PIN-formed family of auxin-efflux transporters. Here we propose that AUXIN RESPONSE FACTOR7 (ARF7) and the ARF7-regulated FOUR LIPS/MYB124 (FLP) transcription factors jointly form a coherent feed-forward motif that mediates the auxin-responsive PIN3 transcription in planta to steer the early steps of lateral root formation. This regulatory mechanism might endow the PIN3 circuitry with a temporal 'memory' of auxin stimuli, potentially maintaining and enhancing the robustness of the auxin flux directionality during lateral root development. The cooperative action between canonical auxin signalling and other transcription factors might constitute a general mechanism by which transcriptional auxin-sensitivity can be regulated at a tissue-specific level.

Cell migration and antigen capture are antagonistic processes coupled by myosin II in dendritic cells - Chabaud, Mélanie; Heuzé, Mélina; Bretou, Marine; Vargas, Pablo; Maiuri, Paolo; Solanes, Paola; Maurin, Mathieu; Terriac, Emmanuel; Le Berre, Maël; Lankar, Danielle; Piolot, Tristan; Adelstein, Robert; et al. (Nature Communications)
The immune response relies on the migration of leukocytes and on their ability to stop in precise anatomical locations to fulfil their task. How leukocyte migration and function are coordinated is unknown. Here we show that in immature dendritic cells, which patrol their environment by engulfing extracellular material, cell migration and antigen capture are antagonistic. This antagonism results from transient enrichment of myosin IIA at the cell front, which disrupts the back-to-front gradient of the motor protein, slowing down locomotion but promoting antigen capture. We further highlight that myosin IIA enrichment at the cell front requires the MHC class II-associated invariant chain (Ii). Thus, by controlling myosin IIA localization, Ii imposes on dendritic cells an intermittent antigen capture behaviour that might facilitate environment patrolling. We propose that the requirement for myosin II in both cell migration and specific cell functions may provide a general mechanism for their coordination in time and space.

An early secretory pathway mediated by gnom-like 1 and gnom is essential for basal polarity establishment in Arabidopsis thaliana - Doyle, Siamsa; Haegera, Ash; Vain, Thomas; Rigala, Adeline; Viotti, Corrado; Łangowskaa, Małgorzata; Maa, Qian; Friml, Jirí; Raikhel, Natasha; Hickse, Glenn; Robert, Stéphanie (PNAS)
Spatial regulation of the plant hormone indole-3-acetic acid (IAA, or auxin) is essential for plant development. Auxin gradient establishment is mediated by polarly localized auxin transporters, including PIN-FORMED (PIN) proteins. Their localization and abundance at the plasma membrane are tightly regulated by endomembrane machinery, especially the endocytic and recycling pathways mediated by the ADP ribosylation factor guanine nucleotide exchange factor (ARF-GEF) GNOM. We assessed the role of the early secretory pathway in establishing PIN1 polarity in Arabidopsis thaliana by pharmacological and genetic approaches. We identified the compound endosidin 8 (ES8), which selectively interferes with PIN1 basal polarity without altering the polarity of apical proteins. ES8 alters the auxin distribution pattern in the root and induces a strong developmental phenotype, including reduced root length. The ARF-GEF- defective mutants gnom-like 1 ( gnl1-1) and gnom ( van7) are significantly resistant to ES8. The compound does not affect recycling or vacuolar trafficking of PIN1 but leads to its intracellular accumulation, resulting in loss of PIN1 basal polarity at the plasma membrane. Our data confirm a role for GNOM in endoplasmic reticulum (ER) - Golgi trafficking and reveal that a GNL1/GNOM-mediated early secretory pathway selectively regulates PIN1 basal polarity establishment in a manner essential for normal plant development.

Novel plasticity rule can explain the development of sensorimotor intelligence - Der, Ralf; Martius, Georg S (PNAS)
Grounding autonomous behavior in the nervous system is a fundamental challenge for neuroscience. In particular, self-organized behavioral development provides more questions than answers. Are there special functional units for curiosity, motivation, and creativity? This paper argues that these features can be grounded in synaptic plasticity itself, without requiring any higher-level constructs. We propose differential extrinsic plasticity (DEP) as a new synaptic rule for self-learning systems and apply it to a number of complex robotic systems as a test case. Without specifying any purpose or goal, seemingly purposeful and adaptive rhythmic behavior is developed, displaying a certain level of sensorimotor intelligence. These surprising results require no systemspecific modifications of the DEP rule. They rather arise from the underlying mechanism of spontaneous symmetry breaking,which is due to the tight brain body environment coupling. The new synaptic rule is biologically plausible and would be an interesting target for neurobiological investigation. We also argue that this neuronal mechanism may have been a catalyst in natural evolution.

Validity of the spin-wave approximation for the free energy of the Heisenberg ferromagnet - Correggi, Michele; Giuliani, Alessandro; Seiringer, Robert (Communications in Mathematical Physics)
We consider the quantum ferromagnetic Heisenberg model in three dimensions, for all spins S ≥ 1/2. We rigorously prove the validity of the spin-wave approximation for the excitation spectrum, at the level of the first non-trivial contribution to the free energy at low temperatures. Our proof comes with explicit, constructive upper and lower bounds on the error term. It uses in an essential way the bosonic formulation of the model in terms of the Holstein-Primakoff representation. In this language, the model describes interacting bosons with a hard-core on-site repulsion and a nearest-neighbor attraction. This attractive interaction makes the lower bound on the free energy particularly tricky: the key idea there is to prove a differential inequality for the two-particle density, which is thereby shown to be smaller than the probability density of a suitably weighted two-particle random process on the lattice.

Unconditional uniqueness for the cubic gross pitaevskii hierarchy via quantum de finetti - Chen, Thomas; Hainzl, Christian; Pavlović, Nataša; Seiringer, Robert (Communications on Pure and Applied Mathematics)
We present a new, simpler proof of the unconditional uniqueness of solutions to the cubic Gross-Pitaevskii hierarchy in ℝ3. One of the main tools in our analysis is the quantum de Finetti theorem. Our uniqueness result is equivalent to the one established in the celebrated works of Erdos, Schlein, and Yau.

Knock-down of synapsin alters cell excitability and action potential waveform by potentiating BK and voltage gated Ca2 currents in Helix serotonergic neurons - Brenes, Oscar; Vandael, David H; Carbone, Emilio; Montarolo, Pier; Ghirardi, Mirella (Neuroscience)
Synapsins (Syns) are an evolutionarily conserved family of presynaptic proteins crucial for the fine-tuning of synaptic function. A large amount of experimental evidences has shown that Syns are involved in the development of epileptic phenotypes and several mutations in Syn genes have been associated with epilepsy in humans and animal models. Syn mutations induce alterations in circuitry and neurotransmitter release, differentially affecting excitatory and inhibitory synapses, thus causing an excitation/inhibition imbalance in network excitability toward hyperexcitability that may be a determinant with regard to the development of epilepsy. Another approach to investigate epileptogenic mechanisms is to understand how silencing Syn affects the cellular behavior of single neurons and is associated with the hyperexcitable phenotypes observed in epilepsy. Here, we examined the functional effects of antisense-RNA inhibition of Syn expression on individually identified and isolated serotonergic cells of the Helix land snail. We found that Helix synapsin silencing increases cell excitability characterized by a slightly depolarized resting membrane potential, decreases the rheobase, reduces the threshold for action potential (AP) firing and increases the mean and instantaneous firing rates, with respect to control cells. The observed increase of Ca2+ and BK currents in Syn-silenced cells seems to be related to changes in the shape of the AP waveform. These currents sustain the faster spiking in Syn-deficient cells by increasing the after hyperpolarization and limiting the Na+ and Ca2+ channel inactivation during repetitive firing. This in turn speeds up the depolarization phase by reaching the AP threshold faster. Our results provide evidence that Syn silencing increases intrinsic cell excitability associated with increased Ca2+ and Ca2+-dependent BK currents in the absence of excitatory or inhibitory inputs.

Birth of a new gene on the Y chromosome of Drosophila melanogaster - Carvalho, Antonio; Vicoso, Beatriz; Russo, Claudia; Swenor, Bonnielin; Clark, Andrew (PNAS)
Contrary to the pattern seen in mammalian sex chromosomes, where most Y-linked genes have X-linked homologs, the Drosophila X and Y chromosomes appear to be unrelated. Most of the Y-linked genes have autosomal paralogs, so autosome-to-Y transposition must be the main source of Drosophila Y-linked genes. Here we show how these genes were acquired. We found a previously unidentified gene (flagrante delicto Y, FDY) that originated from a recent duplication of the autosomal gene vig2 to the Y chromosome of Drosophila melanogaster. Four contiguous genes were duplicated along with vig2, but they became pseudogenes through the accumulation of deletions and transposable element insertions, whereas FDY remained functional, acquired testis-specific expression, and now accounts for ∼20% of the vig2-like mRNA in testis. FDY is absent in the closest relatives of D. melanogaster, and DNA sequence divergence indicates that the duplication to the Y chromosome occurred ∼2 million years ago. Thus, FDY provides a snapshot of the early stages of the establishment of a Y-linked gene and demonstrates how the Drosophila Y has been accumulating autosomal genes.

Galois groups of Schubert problems of lines are at least alternating - Brooks, Christopher; Martin Del Campo Sanchez, Abraham; Sottile, Frank (Transactions of the American Mathematical Society)
We show that the Galois group of any Schubert problem involving lines in projective space contains the alternating group. This constitutes the largest family of enumerative problems whose Galois groups have been largely determined. Using a criterion of Vakil and a special position argument due to Schubert, our result follows from a particular inequality among Kostka numbers of two-rowed tableaux. In most cases, a combinatorial injection proves the inequality. For the remaining cases, we use the Weyl integral formulas to obtain an integral formula for these Kostka numbers. This rewrites the inequality as an integral, which we estimate to establish the inequality.

Magnetic field induced flow pattern reversal in a ferrofluidic Taylor-Couette system - Altmeyer, Sebastian; Do, Younghae; Lai, Ying (Scientific Reports)
We investigate the dynamics of ferrofluidic wavy vortex flows in the counter-rotating Taylor-Couette system, with a focus on wavy flows with a mixture of the dominant azimuthal modes. Without external magnetic field flows are stable and pro-grade with respect to the rotation of the inner cylinder. More complex behaviors can arise when an axial or a transverse magnetic field is applied. Depending on the direction and strength of the field, multi-stable wavy states and bifurcations can occur. We uncover the phenomenon of flow pattern reversal as the strength of the magnetic field is increased through a critical value. In between the regimes of pro-grade and retrograde flow rotations, standing waves with zero angular velocities can emerge. A striking finding is that, under a transverse magnetic field, a second reversal in the flow pattern direction can occur, where the flow pattern evolves into pro-grade rotation again from a retrograde state. Flow reversal is relevant to intriguing phenomena in nature such as geomagnetic reversal. Our results suggest that, in ferrofluids, flow pattern reversal can be induced by varying a magnetic field in a controlled manner, which can be realized in laboratory experiments with potential applications in the development of modern fluid devices.

Reprint of: Weighted straight skeletons in the plane - Biedl, Therese; Held, Martin; Huber, Stefan; Kaaser, Dominik; Palfrader, Peter (Computational Geometry: Theory and Applications)
We investigate weighted straight skeletons from a geometric, graph-theoretical, and combinatorial point of view. We start with a thorough definition and shed light on some ambiguity issues in the procedural definition. We investigate the geometry, combinatorics, and topology of faces and the roof model, and we discuss in which cases a weighted straight skeleton is connected. Finally, we show that the weighted straight skeleton of even a simple polygon may be non-planar and may contain cycles, and we discuss under which restrictions on the weights and/or the input polygon the weighted straight skeleton still behaves similar to its unweighted counterpart. In particular, we obtain a non-procedural description and a linear-time construction algorithm for the straight skeleton of strictly convex polygons with arbitrary weights.

Weighted straight skeletons in the plane - Biedl, Therese; Held, Martin; Huber, Stefan; Kaaser, Dominik; Palfrader, Peter (Computational Geometry: Theory and Applications)
We investigate weighted straight skeletons from a geometric, graph-theoretical, and combinatorial point of view. We start with a thorough definition and shed light on some ambiguity issues in the procedural definition. We investigate the geometry, combinatorics, and topology of faces and the roof model, and we discuss in which cases a weighted straight skeleton is connected. Finally, we show that the weighted straight skeleton of even a simple polygon may be non-planar and may contain cycles, and we discuss under which restrictions on the weights and/or the input polygon the weighted straight skeleton still behaves similar to its unweighted counterpart. In particular, we obtain a non-procedural description and a linear-time construction algorithm for the straight skeleton of strictly convex polygons with arbitrary weights.

A simple algorithm for computing positively weighted straight skeletons of monotone polygons - Biedl, Therese; Held, Martin; Huber, Stefan; Kaaser, Dominik; Palfrader, Peter (Information Processing Letters)
We study the characteristics of straight skeletons of monotone polygonal chains and use them to devise an algorithm for computing positively weighted straight skeletons of monotone polygons. Our algorithm runs in O(nlogn) time and O(n) space, where n denotes the number of vertices of the polygon.

Quantum interference shifts in laser spectroscopy with elliptical polarization - Amaro, Pedro; Fratini, Filippo; Safari, Laleh; Antognini, Aldo; Indelicato, Paul; Pohl, Randolf; Santos, José (Physical Review A - Atomic, Molecular, and Optical Physics)
We investigate the quantum interference shifts between energetically close states, where the state structure is observed by laser spectroscopy. We report a compact and analytical expression that models the quantum interference induced shift for any admixture of circular polarization of the incident laser and angle of observation. An experimental scenario free of quantum interference can thus be predicted with this formula. Although this study is exemplified here for muonic deuterium, it can be applied to any other laser spectroscopy measurement of ns-n′p frequencies of a nonrelativistic atomic system, via an ns→n′p→n′′s scheme.

Strategies of seedlings to overcome their sessile nature: Auxin in mobility control - Žádníková, Petra; Smet, Dajo; Zhu, Qiang; Van Der Straeten, Dominique; Benková, Eva (Frontiers in Plant Science)
Plants are sessile organisms that are permanently restricted to their site of germination. To compensate for their lack of mobility, plants evolved unique mechanisms enabling them to rapidly react to ever changing environmental conditions and flexibly adapt their postembryonic developmental program. A prominent demonstration of this developmental plasticity is their ability to bend organs in order to reach the position most optimal for growth and utilization of light, nutrients, and other resources. Shortly after germination, dicotyledonous seedlings form a bended structure, the so-called apical hook, to protect the delicate shoot meristem and cotyledons from damage when penetrating through the soil. Upon perception of a light stimulus, the apical hook rapidly opens and the photomorphogenic developmental program is activated. After germination, plant organs are able to align their growth with the light source and adopt the most favorable orientation through bending, in a process named phototropism. On the other hand, when roots and shoots are diverted from their upright orientation, they immediately detect a change in the gravity vector and bend to maintain a vertical growth direction. Noteworthy, despite the diversity of external stimuli perceived by different plant organs, all plant tropic movements share a common mechanistic basis: differential cell growth. In our review, we will discuss the molecular principles underlying various tropic responses with the focus on mechanisms mediating the perception of external signals, transduction cascades and downstream responses that regulate differential cell growth and consequently, organ bending. In particular, we highlight common and specific features of regulatory pathways in control of the bending of organs and a role for the plant hormone auxin as a key regulatory component.

Hanani-Tutte for radial planarity - Fulek, Radoslav; Pelsmajer, Michael; Schaefer, Marcus
A drawing of a graph G is radial if the vertices of G are placed on concentric circles C1, . . . , Ck with common center c, and edges are drawn radially: every edge intersects every circle centered at c at most once. G is radial planar if it has a radial embedding, that is, a crossing- free radial drawing. If the vertices of G are ordered or partitioned into ordered levels (as they are for leveled graphs), we require that the assignment of vertices to circles corresponds to the given ordering or leveling. We show that a graph G is radial planar if G has a radial drawing in which every two edges cross an even number of times; the radial embedding has the same leveling as the radial drawing. In other words, we establish the weak variant of the Hanani-Tutte theorem for radial planarity. This generalizes a result by Pach and Tóth.

Representing directed trees as straight skeletons - Aichholzer, Oswin; Biedl, Therese; Hackl, Thomas; Held, Martin; Huber, Stefan; Palfrader, Peter; Vogtenhuber, Birgit (Graph Drawing and Network Visualization)
The straight skeleton of a polygon is the geometric graph obtained by tracing the vertices during a mitered offsetting process. It is known that the straight skeleton of a simple polygon is a tree, and one can naturally derive directions on the edges of the tree from the propagation of the shrinking process. In this paper, we ask the reverse question: Given a tree with directed edges, can it be the straight skeleton of a polygon? And if so, can we find a suitable simple polygon? We answer these questions for all directed trees where the order of edges around each node is fixed.

Vertical visibility among parallel polygons in three dimensions - Fulek, Radoslav; Radoičić, Radoš (Graph Drawing and Network Visualization)
Let C={C1,...,Cn} denote a collection of translates of a regular convex k-gon in the plane with the stacking order. The collection C forms a visibility clique if for everyi < j the intersection Ci and (Ci ∩ Cj)\⋃i<l<jCl =∅.elements that are stacked between them, i.e., We show that if C forms a visibility clique its size is bounded from above by O(k4) thereby improving the upper bound of 22k from the aforementioned paper. We also obtain an upper bound of 22(k/2)+2 on the size of a visibility clique for homothetes of a convex (not necessarily regular) k-gon.

The Hanoi omega-automata format - Babiak, Tomáš; Blahoudek, František; Duret Lutz, Alexandre; Klein, Joachim; Kretinsky, Jan; Mueller, Daniel; Parker, David; Strejček, Jan
We propose a flexible exchange format for ω-automata, as typically used in formal verification, and implement support for it in a range of established tools. Our aim is to simplify the interaction of tools, helping the research community to build upon other people’s work. A key feature of the format is the use of very generic acceptance conditions, specified by Boolean combinations of acceptance primitives, rather than being limited to common cases such as Büchi, Streett, or Rabin. Such flexibility in the choice of acceptance conditions can be exploited in applications, for example in probabilistic model checking, and furthermore encourages the development of acceptance-agnostic tools for automata manipulations. The format allows acceptance conditions that are either state-based or transition-based, and also supports alternating automata.

Abstraction-based parameter synthesis for multiaffine systems - Bogomolov, Sergiy; Schilling, Christian; Bartocci, Ezio; Batt, Grégory; Kong, Hui; Grosu, Radu
Multiaffine hybrid automata (MHA) represent a powerful formalism to model complex dynamical systems. This formalism is particularly suited for the representation of biological systems which often exhibit highly non-linear behavior. In this paper, we consider the problem of parameter identification for MHA. We present an abstraction of MHA based on linear hybrid automata, which can be analyzed by the SpaceEx model checker. This abstraction enables a precise handling of time-dependent properties. We demonstrate the potential of our approach on a model of a genetic regulatory network and a myocyte model.

The complexity of synthesis from probabilistic components - Chatterjee, Krishnendu; Doyen, Laurent; Vardi, Moshe (42nd International Colloquium)
The synthesis problem asks for the automatic construction of a system from its specification. In the traditional setting, the system is “constructed from scratch” rather than composed from reusable components. However, this is rare in practice, and almost every non-trivial software system relies heavily on the use of libraries of reusable components. Recently, Lustig and Vardi introduced dataflow and controlflow synthesis from libraries of reusable components. They proved that dataflow synthesis is undecidable, while controlflow synthesis is decidable. The problem of controlflow synthesis from libraries of probabilistic components was considered by Nain, Lustig and Vardi, and was shown to be decidable for qualitative analysis (that asks that the specification be satisfied with probability 1). Our main contribution for controlflow synthesis from probabilistic components is to establish better complexity bounds for the qualitative analysis problem, and to show that the more general quantitative problem is undecidable. For the qualitative analysis, we show that the problem (i) is EXPTIME-complete when the specification is given as a deterministic parity word automaton, improving the previously known 2EXPTIME upper bound; and (ii) belongs to UP ∩ coUP and is parity-games hard, when the specification is given directly as a parity condition on the components, improving the previously known EXPTIME upper bound.

Perturbed hippocampal synaptic inhibition and γ-oscillations in a neuroligin-4 knockout mouse model of autism - Hammer, Matthieu; Krueger Burg, Dilja; Tuffy, Liam; Cooper, Benjamin; Taschenberger, Holger; Goswami, Sarit; Ehrenreich, Hannelore; Jonas, Peter M; Varoqueaux, Frederique; Rhee, Jeong; Brose, Nils (Cell Reports)
Loss-of-function mutations in the synaptic adhesion protein Neuroligin-4 are among the most common genetic abnormalities associated with autism spectrum disorders, but little is known about the function of Neuroligin-4 and the consequences of its loss. We assessed synaptic and network characteristics in Neuroligin-4 knockout mice, focusing on the hippocampus as a model brain region with a critical role in cognition and memory, and found that Neuroligin-4 deletion causes subtle defects of the protein composition and function of GABAergic synapses in the hippocampal CA3 region. Interestingly, these subtle synaptic changes are accompanied by pronounced perturbations of γ-oscillatory network activity, which has been implicated in cognitive function and is altered in multiple psychiatric and neurodevelopmental disorders. Our data provide important insights into the mechanisms by which Neuroligin-4-dependent GABAergic synapses may contribute to autism phenotypes and indicate new strategies for therapeutic approaches.

Strength and duration of perisomatic GABAergic inhibition depend on distance between synaptically connected cells - Strüber, Michael; Jonas, Peter M; Bartos, Marlene (PNAS)
GABAergic perisoma-inhibiting fast-spiking interneurons (PIIs) effectively control the activity of large neuron populations by their wide axonal arborizations. It is generally assumed that the output of one PII to its target cells is strong and rapid. Here, we show that, unexpectedly, both strength and time course of PII-mediated perisomatic inhibition change with distance between synaptically connected partners in the rodent hippocampus. Synaptic signals become weaker due to lower contact numbers and decay more slowly with distance, very likely resulting from changes in GABAA receptor subunit composition. When distance-dependent synaptic inhibition is introduced to a rhythmically active neuronal network model, randomly driven principal cell assemblies are strongly synchronized by the PIIs, leading to higher precision in principal cell spike times than in a network with uniform synaptic inhibition.

Construction of a robust and sensitive arginine biosensor through ancestral protein reconstruction - Whitfield, Jason; Zhang, William; Herde, Michel; Clifton, Ben; Radziejewski, Johanna; Janovjak, Harald L; Henneberger, Christian; Jackson, Colin (Protein Science)
Biosensors for signaling molecules allow the study of physiological processes by bringing together the fields of protein engineering, fluorescence imaging, and cell biology. Construction of genetically encoded biosensors generally relies on the availability of a binding "core" that is both specific and stable, which can then be combined with fluorescent molecules to create a sensor. However, binding proteins with the desired properties are often not available in nature and substantial improvement to sensors can be required, particularly with regard to their durability. Ancestral protein reconstruction is a powerful protein-engineering tool able to generate highly stable and functional proteins. In this work, we sought to establish the utility of ancestral protein reconstruction to biosensor development, beginning with the construction of an l-arginine biosensor. l-arginine, as the immediate precursor to nitric oxide, is an important molecule in many physiological contexts including brain function. Using a combination of ancestral reconstruction and circular permutation, we constructed a Förster resonance energy transfer (FRET) biosensor for l-arginine (cpFLIPR). cpFLIPR displays high sensitivity and specificity, with a Kd of ∼14 μM and a maximal dynamic range of 35%. Importantly, cpFLIPR was highly robust, enabling accurate l-arginine measurement at physiological temperatures. We established that cpFLIPR is compatible with two-photon excitation fluorescence microscopy and report l-arginine concentrations in brain tissue.

Cellular cooperation with shift updating and repulsion - Pavlogiannis, Andreas; Chatterjee, Krishnendu; Adlam, Ben; Nowak, Martin (Scientific Reports)
Population structure can facilitate evolution of cooperation. In a structured population, cooperators can form clusters which resist exploitation by defectors. Recently, it was observed that a shift update rule is an extremely strong amplifier of cooperation in a one dimensional spatial model. For the shift update rule, an individual is chosen for reproduction proportional to fecundity; the offspring is placed next to the parent; a random individual dies. Subsequently, the population is rearranged (shifted) until all individual cells are again evenly spaced out. For large population size and a one dimensional population structure, the shift update rule favors cooperation for any benefit-to-cost ratio greater than one. But every attempt to generalize shift updating to higher dimensions while maintaining its strong effect has failed. The reason is that in two dimensions the clusters are fragmented by the movements caused by rearranging the cells. Here we introduce the natural phenomenon of a repulsive force between cells of different types. After a birth and death event, the cells are being rearranged minimizing the overall energy expenditure. If the repulsive force is sufficiently high, shift becomes a strong promoter of cooperation in two dimensions.

Single-cell screening of photosynthetic growth and lactate production by cyanobacteria - Hammar, Petter; Angermayr, Andreas; Sjostrom, Staffan; Van Der Meer, Josefin; Hellingwerf, Klaas; Hudson, Elton; Joensson, Hakaan (Biotechnology for Biofuels)
Background Photosynthetic cyanobacteria are attractive for a range of biotechnological applications including biofuel production. However, due to slow growth, screening of mutant libraries using microtiter plates is not feasible. Results We present a method for high-throughput, single-cell analysis and sorting of genetically engineered l-lactate-producing strains of Synechocystis sp. PCC6803. A microfluidic device is used to encapsulate single cells in picoliter droplets, assay the droplets for l-lactate production, and sort strains with high productivity. We demonstrate the separation of low- and high-producing reference strains, as well as enrichment of a more productive l-lactate-synthesizing population after UV-induced mutagenesis. The droplet platform also revealed population heterogeneity in photosynthetic growth and lactate production, as well as the presence of metabolically stalled cells. Conclusions The workflow will facilitate metabolic engineering and directed evolution studies and will be useful in studies of cyanobacteria biochemistry and physiology.

Microstructures to control elasticity in 3D printing - Schumacher, Christian; Bickel, Bernd; Rys, Jan; Marschner, Steve; Daraio, Chiara; Gross, Markus
We propose a method for fabricating deformable objects with spatially varying elasticity using 3D printing. Using a single, relatively stiff printer material, our method designs an assembly of smallscale microstructures that have the effect of a softer material at the object scale, with properties depending on the microstructure used in each part of the object. We build on work in the area of metamaterials, using numerical optimization to design tiled microstructures with desired properties, but with the key difference that our method designs families of related structures that can be interpolated to smoothly vary the material properties over a wide range. To create an object with spatially varying elastic properties, we tile the object's interior with microstructures drawn from these families, generating a different microstructure for each cell using an efficient algorithm to select compatible structures for neighboring cells. We show results computed for both 2D and 3D objects, validating several 2D and 3D printed structures using standard material tests as well as demonstrating various example applications.

Double bubbles sans toil and trouble: discrete circulation-preserving vortex sheets for soap films and foams - Da, Fang; Batty, Christopher; Wojtan, Christopher J; Grinspun, Eitan
Simulating the delightful dynamics of soap films, bubbles, and foams has traditionally required the use of a fully three-dimensional many-phase Navier-Stokes solver, even though their visual appearance is completely dominated by the thin liquid surface. We depart from earlier work on soap bubbles and foams by noting that their dynamics are naturally described by a Lagrangian vortex sheet model in which circulation is the primary variable. This leads us to derive a novel circulation-preserving surface-only discretization of foam dynamics driven by surface tension on a non-manifold triangle mesh. We represent the surface using a mesh-based multimaterial surface tracker which supports complex bubble topology changes, and evolve the surface according to the ambient air flow induced by a scalar circulation field stored on the mesh. Surface tension forces give rise to a simple update rule for circulation, even at non-manifold Plateau borders, based on a discrete measure of signed scalar mean curvature. We further incorporate vertex constraints to enable the interaction of soap films with wires. The result is a method that is at once simple, robust, and efficient, yet able to capture an array of soap films behaviors including foam rearrangement, catenoid collapse, blowing bubbles, and double bubbles being pulled apart.

Effectiveness of structural restrictions for hybrid CSPs - Kolmogorov, Vladimir; Rolinek, Michal; Takhanov, Rustem (26th International Symposium)
Constraint Satisfaction Problem (CSP) is a fundamental algorithmic problem that appears in many areas of Computer Science. It can be equivalently stated as computing a homomorphism R→ΓΓ between two relational structures, e.g. between two directed graphs. Analyzing its complexity has been a prominent research direction, especially for the fixed template CSPs where the right side ΓΓ is fixed and the left side R is unconstrained. Far fewer results are known for the hybrid setting that restricts both sides simultaneously. It assumes that R belongs to a certain class of relational structures (called a structural restriction in this paper). We study which structural restrictions are effective, i.e. there exists a fixed template ΓΓ (from a certain class of languages) for which the problem is tractable when R is restricted, and NP-hard otherwise. We provide a characterization for structural restrictions that are closed under inverse homomorphisms. The criterion is based on the chromatic number of a relational structure defined in this paper; it generalizes the standard chromatic number of a graph. As our main tool, we use the algebraic machinery developed for fixed template CSPs. To apply it to our case, we introduce a new construction called a “lifted language”. We also give a characterization for structural restrictions corresponding to minor-closed families of graphs, extend results to certain Valued CSPs (namely conservative valued languages), and state implications for (valued) CSPs with ordered variables and for the maximum weight independent set problem on some restricted families of graphs.

A stream function solver for liquid simulations - Ando, Ryoichi; Thuerey, Nils; Wojtan, Christopher J
This paper presents a liquid simulation technique that enforces the incompressibility condition using a stream function solve instead of a pressure projection. Previous methods have used stream function techniques for the simulation of detailed single-phase flows, but a formulation for liquid simulation has proved elusive in part due to the free surface boundary conditions. In this paper, we introduce a stream function approach to liquid simulations with novel boundary conditions for free surfaces, solid obstacles, and solid-fluid coupling. Although our approach increases the dimension of the linear system necessary to enforce incompressibility, it provides interesting and surprising benefits. First, the resulting flow is guaranteed to be divergence-free regardless of the accuracy of the solve. Second, our free-surface boundary conditions guarantee divergence-free motion even in the un-simulated air phase, which enables two-phase flow simulation by only computing a single phase. We implemented this method using a variant of FLIP simulation which only samples particles within a narrow band of the liquid surface, and we illustrate the effectiveness of our method for detailed two-phase flow simulations with complex boundaries, detailed bubble interactions, and two-way solid-fluid coupling.

Learning shape placements by example - Guerrero, Paul; Jeschke, Stefan; Wimmer, Michael; Wonka, Peter
We present a method to learn and propagate shape placements in 2D polygonal scenes from a few examples provided by a user. The placement of a shape is modeled as an oriented bounding box. Simple geometric relationships between this bounding box and nearby scene polygons define a feature set for the placement. The feature sets of all example placements are then used to learn a probabilistic model over all possible placements and scenes. With this model, we can generate a new set of placements with similar geometric relationships in any given scene. We introduce extensions that enable propagation and generation of shapes in 3D scenes, as well as the application of a learned modeling session to large scenes without additional user interaction. These concepts allow us to generate complex scenes with thousands of objects with relatively little user interaction.

Cytokinin response factors regulate PIN-FORMED auxin transporters - Šimášková, Mária; O'Brien, José; Khan-Djamei, Mamoona; Van Noorden, Giel; Ötvös, Krisztina; Vieten, Anne; De Clercq, Inge; Van Haperen, Johanna; Cuesta, Candela; Hoyerová, Klára; Vanneste, Steffen; Marhavy, Peter; et al. (Nature Communications)
Auxin and cytokinin are key endogenous regulators of plant development. Although cytokinin-mediated modulation of auxin distribution is a developmentally crucial hormonal interaction, its molecular basis is largely unknown. Here we show a direct regulatory link between cytokinin signalling and the auxin transport machinery uncovering a mechanistic framework for cytokinin-auxin cross-talk. We show that the CYTOKININ RESPONSE FACTORS (CRFs), transcription factors downstream of cytokinin perception, transcriptionally control genes encoding PIN-FORMED (PIN) auxin transporters at a specific PIN CYTOKININ RESPONSE ELEMENT (PCRE) domain. Removal of this cis-regulatory element effectively uncouples PIN transcription from the CRF-mediated cytokinin regulation and attenuates plant cytokinin sensitivity. We propose that CRFs represent a missing cross-talk component that fine-tunes auxin transport capacity downstream of cytokinin signalling to control plant development.

Clustered planarity testing revisited - Fulek, Radoslav; Kynčl, Jan; Malinovič, Igor; Pálvölgyi, Dömötör (Electronic Journal of Combinatorics)
The Hanani-Tutte theorem is a classical result proved for the first time in the 1930s that characterizes planar graphs as graphs that admit a drawing in the plane in which every pair of edges not sharing a vertex cross an even number of times. We generalize this result to clustered graphs with two disjoint clusters, and show that a straightforward extension to flat clustered graphs with three or more disjoint clusters is not possible. For general clustered graphs we show a variant of the Hanani-Tutte theorem in the case when each cluster induces a connected subgraph. Di Battista and Frati proved that clustered planarity of embedded clustered graphs whose every face is incident to at most five vertices can be tested in polynomial time. We give a new and short proof of this result, using the matroid intersection algorithm.

A generalized model for optimal transport of images including dissipation and density modulation - Maas, Jan; Rumpf, Martin; Schönlieb, Carola; Simon, Stefan (ESAIM: Mathematical Modelling and Numerical Analysis)
In this paper the optimal transport and the metamorphosis perspectives are combined. For a pair of given input images geodesic paths in the space of images are defined as minimizers of a resulting path energy. To this end, the underlying Riemannian metric measures the rate of transport cost and the rate of viscous dissipation. Furthermore, the model is capable to deal with strongly varying image contrast and explicitly allows for sources and sinks in the transport equations which are incorporated in the metric related to the metamorphosis approach by Trouvé and Younes. In the non-viscous case with source term existence of geodesic paths is proven in the space of measures. The proposed model is explored on the range from merely optimal transport to strongly dissipative dynamics. For this model a robust and effective variational time discretization of geodesic paths is proposed. This requires to minimize a discrete path energy consisting of a sum of consecutive image matching functionals. These functionals are defined on corresponding pairs of intensity functions and on associated pairwise matching deformations. Existence of time discrete geodesics is demonstrated. Furthermore, a finite element implementation is proposed and applied to instructive test cases and to real images. In the non-viscous case this is compared to the algorithm proposed by Benamou and Brenier including a discretization of the source term. Finally, the model is generalized to define discrete weighted barycentres with applications to textures and objects.

Key-homomorphic constrained pseudorandom functions - Banerjee, Abishek; Fuchsbauer, Georg; Peikert, Chris; Pietrzak, Krzysztof Z; Stevens, Sophie (12th Theory of Cryptography Conference)
A pseudorandom function (PRF) is a keyed function F : K × X → Y where, for a random key k ∈ K, the function F(k, ·) is indistinguishable from a uniformly random function, given black-box access. A key-homomorphic PRF has the additional feature that for any keys k, k' and any input x, we have F(k+k', x) = F(k, x)⊕F(k', x) for some group operations +,⊕ on K and Y, respectively. A constrained PRF for a family of setsS ⊆ P(X) has the property that, given any key k and set S ∈ S, one can efficiently compute a “constrained” key kS that enables evaluation of F(k, x) on all inputs x ∈ S, while the values F(k, x) for x /∈ S remain pseudorandom even given kS. In this paper we construct PRFs that are simultaneously constrained and key homomorphic, where the homomorphic property holds even for constrained keys. We first show that the multilinear map-based bit-fixing and circuit-constrained PRFs of Boneh and Waters (Asiacrypt 2013) can be modified to also be keyhomomorphic. We then show that the LWE-based key-homomorphic PRFs of Banerjee and Peikert (Crypto 2014) are essentially already prefix-constrained PRFs, using a (non-obvious) definition of constrained keys and associated group operation. Moreover, the constrained keys themselves are pseudorandom, and the constraining and evaluation functions can all be computed in low depth. As an application of key-homomorphic constrained PRFs,we construct a proxy re-encryption schemewith fine-grained access control. This scheme allows storing encrypted data on an untrusted server, where each file can be encrypted relative to some attributes, so that only parties whose constrained keys match the attributes can decrypt. Moreover, the server can re-key (arbitrary subsets of) the ciphertexts without learning anything about the plaintexts, thus permitting efficient and finegrained revocation.